GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 21714542 species occurrences available in GBIF matching the query: Geometry: POLYGON((-98.4375 1.406108,-62.578125 20.632784,-40.78125 9.102096,-28.125 -8.407168,-33.046875 -29.535229,-47.109375 -45.089035,-57.656249 -58.077876,-72.421875 -60.586967,-98.4375 1.406108)). The dataset includes 21714542 records from 2183 constituent datasets: 1003 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 1426 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 92 records from Naturalis Biodiversity Center (NL) - Crustacea. 216 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 336 records from Especies de Anacroneuria (Insecta: Plecoptera: Perlidae) de Colombia, depositadas en el Museo de Entomología de la Universidad del Valle (Cali, Colombia). 13593 records from Mollusca of Costa Rica (INBio). 3 records from Phthiraptera. 12704 records from The molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 6 records from Ortopthera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 218 records from Colección de Salamandras Museo de La Salle Bogotá (MLS). 142 records from Tejidos de quirópteros de tres localidades del caribe colombiano. 11 records from Ghent University - Zoology Museum - Vertebrate collection. 206 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 7 records from Peckoltia sabaji, a new species from the Guyana Shield (Siluriformes: Loricariidae).. 2494 records from SPFw - Xiloteca do Instituto de Biociências da Universidade de São Paulo. 473 records from Equinodermos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMeq-UV). 24496 records from Plan de vertebrados de la Patagonia. 167178 records from International Barcode of Life project (iBOL). 2661 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Tayrona. 2 records from Benthic hard-bottom communities abundance at X-Huinay in 2010. 3 records from Redescription, lectotype designation and new records of Anastrepha luederwaldti Lima (Diptera, Tephritidae). 385 records from (Appendix E) Size measurements of Selenopemphix undulata sp. nov. in ODP Site 202-1233. 2 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 118 records from A Tenebrionid beetle’s dataset (Coleoptera, Tenebrionidae) from Peninsula Valdés (Chubut, Argentina). 6060 records from Free-living Nematodes from Patagonia coastal lagoons (Chubut, Santa Cruz, Argentina).. 2217 records from JOI - Herbário Joinvillea. 1 records from University of Calgary Herbarium. 8151 records from ISE - Herbário ISE. 10030 records from Free-living marine Nematodes from San Julián bay (Santa Cruz, Argentine), 2009.. 115 records from USGS SESC - Virgin Islands - Herpetofauna - 2001-2002. 150148 records from A global database for the distributions of crop wild relatives. 156 records from A Review of the Jumping Spider Fauna (Araneae: Salticidae) of Chile. 10 records from Description of a new Penaeidae (Decapoda: Dendrobranchiata) species, Farfantepenaeus isabelae sp. nov.. 7 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 1570 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 2037 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 190 records from Herpetofauna laguna El Tinije. 8223 records from HUEM - Herbário da Universidade Estadual de Maringá. 8 records from Kirkegaardia (Polychaeta, Cirratulidae), new name for Monticellina Laubier, preoccupied in the Rhabdocoela, together with new records and descriptions of eight previously known and sixteen new species from the Atlantic, Pacific, and Southern Oceans. 10436 records from HUFU - Herbarium Uberlandense. 10644 records from Phanerogamic Botanical Collections (S). 541 records from Mollusca collection of National Museum of Nature and Science. 77 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 279 records from Dieta del Piquero Café (Sula leucogaster etesiaca) en el Parque Nacional Natural Gorgona, Pacífico colombiano.. 19723 records from MVZ Herp Collection (Arctos). 3 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 1 records from New morphological information on Simulium wygodzinskyorum Coscarón & Py-Daniel, 1989 (Diptera: Simuliidae). 6075 records from University of Vienna, Institute for Botany - Herbarium WU. 9302 records from Ants from the Paraguayan dry Chaco. 2147 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 1997 records from Aves de la cuenca media del río Bogotá. 1300 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del río Cajambre (Guandal), municipio de Buenaventura, Valle del Cauca. 3965 records from UFG - Herbário da Universidade Federal de Goiás. 3 records from A new species of Simopelta (Hymenoptera: Formicidae: Ponerinae) from Brazil and Costa Rica. 5016 records from MFS - Herbário Profª. Drª. Marlene Freitas da Silva. 437 records from Colección nacional de palmas de Colombia - JBQ. 58 records from ZUEC-AST - Coleção de Asteroidea do Museu de Zoologia da UNICAMP. 934 records from Colección de Entomología - Diptera - Ceratopogonidae. 603 records from Registros preliminares del "Catálogo de cangrejos ermitaños del mar Caribe colombiano". 16 records from Avistamiento de Aves Corregimientos de Juanchaco y Ladrilleros, Buenaventura, Valle del Cauca - Septiembre 2016. 304 records from Succession of benthic hard-bottom communities abundance at station Errina2012_IS_solar2. 1808 records from University of Amsterdam (NL) - Páramo vegetation research, Ecuador.. 10 records from Inventarios de Murciélagos Pauto M, La Primavera, Yopal, Casanare. 2939 records from LSUM Bernard Lowy Mycological Herbarium at Louisiana State University - Fungi. 1 records from Review of the genus Hannemania (Acari: Leeuwenhoekiidae) with description the two new species in amphibians from Chile. 20192 records from MVZ Mammal Collection (Arctos). 2741 records from Nematoda of Costa Rica (INBio). 16 records from Australian National Wildlife Collection provider for OZCAM. 42 records from (Table 2) Benthic foraminifers at DSDP Hole 72-515A. 52 records from ecoscope_observation_database. 4251 records from Aves de la cuenca media del río Chambery, Caldas. 12 records from Colección de Exhibición de Fósiles del Museo de Ciencias de la Universidad El Bosque. 568 records from PolE At Sea Observations of Birds and Marine Mammals during PS 81 (ANT-XXIX/4). 12678 records from Coleção de Aves do Museu Nacional / UFRJ. 1260 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 87031 records from LACM Entomology Collection. 1 records from Bryophyte herbarium, Tromsø Museum. 807 records from Aquatic Insects from the Caatinga: checklists and diversity assessments of Ubajara (Ceará State) and Sete Cidades (Piauí State) National Parks, Northeastern Brazil. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 8367 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 350 records from Orthopteroidea. 44407 records from IAC - Herbário do Instituto Agronômico de Campinas. 117 records from A taxonomic revision of the Neotropical myrmicine ant genus Lachnomyrmex Wheeler (Hymenoptera: Formicidae). 2 records from A new two-pored species of Amphisbaena (Squamata, Amphisbaenidae) from the Brazilian Cerrado, with a key to the two-pored species of Amphisbaena. 1010 records from Flora vascular de las llanuras aluviales del bajo río Nechí (Antioquia, Colombia). 12885 records from Bee Biology and Systematics Laboratory. 3072 records from UPRM Invertebrate Collection. 4 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 1 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 6 records from Four new species of Lorryia (Acari: Tydeidae) associated with Hevea brasiliensis Muell. Arg. (Euphorbiaceae) in Brazil. 13159 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 9 records from Portuguese Seaweeds. 13 records from Computarización de la Colección Nacional de Crustáceos del Instituto de Biología, UNAM y elaboración de su catálogo. 8778 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 476 records from Caracterización Aves IAI-GAICA: Proyecto Cambio Climático. 711 records from Colección Hidrobiológica del Chocó. 31633 records from AntWeb. 23 records from Retrocitomyia Lopes, 1982 (Diptera: Sarcophagidae): new species, new records, key to males, and an updated catalog. 1290 records from Diptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 3 records from New records of doryctine wasps (Hymenoptera: Braconidae) from Argentina, with the description of Shawius diiorioi Martínez sp. nov.. 7 records from CAS Entomology (ENT). 197 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 96 records from HTSA-Carpoteca - Carpoteca do Trópico Semiárido. 2 records from A distinctive new species of gnatcatcher in the Polioptila guianensis complex (Aves, Polioptilidae) from western Amazonian Brazil. 218 records from Zoology (Museum of Evolution - Uppsala). 103885 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 395 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 110 records from PlutoF platform observations. 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 20 records from Herbarium Senckenbergianum (GLM) - Lichenes. 1412 records from Biodiversity Research and Teaching Collections - TCWC Marine Invertebrates. 7 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 11419 records from SPSF - Herbário Dom Bento José Pickel. 1 records from Out of the Neotropics: newly discovered relictual species sheds light on the biogeographical history of spider ants (Leptomyrmex, Dolichoderinae, Formicidae). 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 26034 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 12944 records from ZUEC-AMP - Coleção de Anfíbios do Museu de Zoologia da UNICAMP. 210 records from PRECIS. 1128 records from Colección de Crustacea del Museo Nacional de Historia Natural de Chile. 8 records from Colección de Referencia de Urocordados del Museo de Ciencias de la Universidad El Bosque. 541 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 5 records from CSIRO Ichthyology provider for OZCAM. 159690 records from Herbario Nacional Colombiano (COL). 43 records from New species and synonymies in Xenopygus Bernhauer (Coleoptera: Staphylinidae: Staphylinini). 67 records from Evaluación bioecológica y ambiental de las áreas arrecifales del Caribe colombiano. 4 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 1427 records from Colección de aves del Museo de Historia Natural de la Pontificia Universidad Javeriana. 2 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 37554 records from Fishbase. 4 records from A new genus of freshwater crab of the tribe Kingsleyini Bott, 1970 (Crustacea: Decapoda: Brachyura: Pseudothelphusidae) with description of a new species from Mato Grosso, Brazil. 3884 records from Funed-Pol - Coleção de lâminas de grãos de pólen. 4 records from Pseudonemesia tabiskey, a new species of Pseudonemesia Caporiacco 1955 and new ultramorphological data for the Microstigmatinae (Araneae: Microstigmatidae). 5 records from Description of two new species of the catfish genus Trichomycterus from southeastern Brazil (Siluriformes: Trichomycteridae).. 487 records from UTEP Plants (Arctos). 201 records from Occurrence records of southern African aquatic biodiversity. 12 records from Paläontologie Marburg. 185 records from Macrozoobenthos abundance of the intertidal zone of a sandy beach at the Island Algodoal-Maiandeua, Pará, Brazil. 4 records from The Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 378 records from Review of Dissomphalus Ashmead, 1893 (Hymenoptera, Bethylidae) from Espíri- to Santo, Brazil, with description of twenty-one new species. 34964 records from SPF - Herbário da Universidade de São Paulo. 14 records from The Neotropical tanyderid Araucoderus gloriosus (Alexander) (Diptera, Tanyderidae), with description of the egg, larva and pupa, redescription of adults, and notes on natural history. 5771 records from Segunda caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 28 records from Cerambycidae (Insecta: Coleoptera) of Quixadá, Ceará State, Brazil: new records and new species. 143 records from SANT Herbarium vascular plants collection. 1892 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 1 records from Begonia jaguarensis L. Kollmann, R. S. Lopes & Peixoto (Begoniaceae), a new species from North of Espírito Santo State, Brazil. 5642 records from KUBI Mammalogy Collection. 16 records from Projeto Abrace o Boto Cinza. 190 records from Biological Reference Collections ICM CSIC. 1715 records from (Appendix) Planktonic foraminifera abundances in ODP Site 138-847B. 7 records from Benthic hard-bottom communities abundance at X-Huinay in 2012. 354 records from Colección de Entomología - Arthropoda. 17363 records from UFP - Herbário UFP - Geraldo Mariz. 3237 records from Colección de Ornitología - Museo de Ciencias Naturales de La Salle. 1461 records from University of Amsterdam (NL) - Páramo pollen reference collection. 447 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 61 records from Registros restauración ecológica- Magdalena medio. 8 records from Three new species of seasonal killifishes of the Simpsonichthys antenori species group (Teleostei: Cyprinodontiformes: Rivulidae) from the rio São Francisco basin, Brazil.. 7 records from NPL collections. 140 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 35857 records from Colección Herbario Federico Medem Bogotá - FMB. 6 records from Three new species of Claudiella Reichardt & Vanin, 1976 (Coleoptera, Torridincolidae) from Brazil. 19651 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 124 records from (Appendix A1) Cenomanian benthic foraminifera of ODP Hole 207-1258A. 4 records from SJRP-Bryophyta - Herbário de Bryophyta de São José do Rio Preto. 146 records from Checklist of aquatic and marshy Monocotyledons from the Araguaia River basin, Brazilian Cerrado. 4 records from Palaeobiology - Vertebrate Fossils Collection - Non Mammalia - Royal Ontario Museum. 14 records from Cercle des mycologues de Montréal Fungarium (CMMF). 3261 records from MBML-Mamiferos - Coleção de Mamíferos. 815 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 198 records from Segunda caracterización biológica de hormigas cazadoras del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 17 records from On the genus Elasmopus Costa, 1853 from the Northeastern Coast of Brazil with five new species and new records. 2072 records from Crustáceos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CERBMcr-UV). 76 records from A taxonomic review of the genus Azteca (Hymenoptera: Formicidae) in Costa Rica and a global revision of the aurita group.. 6139 records from HERBAM - Herbário da Amazônia Meridional. 5079 records from Caracterización de la avifauna de las cuencas de los Ríos Cañas (Dibulla–Guajira), Garupal (Valledupar–Cesar), Arroyo Grande (San Juan de Nepomuceno–Bolívar), Aipe (Huila), Yaví (Tolima), Dagua (Valle del Cauca) como insumo para la identificación de oportunidades de conservación y de recuperación de servicios ecosistémicos del bosque seco.. 23373 records from Herbario Pontificia Universidad Javeriana. 21276 records from ICN - Herbário do Instituto de Ciências Naturais. 4 records from Contributions to the knowledge of the biodiversity of Heteroptera (Insecta) in the Southern Cone, Argentina. 8101 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 3733 records from ZUEC-GAS - Coleção de Gastropoda do Museu de Zoologia da UNICAMP. 14 records from Inventario Herpetológico Pauto J, Rincón del Soldado, Yopal, Casanare. 4065 records from Colección Herpetológica del Museo Nacional de Historia Natural de Chile. 81715 records from Herbario Universidad de Antioquia (HUA). 8227 records from URM - Herbário Pe. Camille Torrand. 29 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 3 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 25 records from Revision of the genera Pareuthria Strebel, 1905, Glypteuthria Strebel, 1905 and Meteuthria Thiele, 1912 (Gastropoda: Buccinulidae) with the description of three new genera and two new species from Southwestern Atlantic waters. 8 records from Five new feather mites of the subfamily Pterodectinae (Acariformes: Astigmata: Proctophyllodidae) from passerines and hummingbirds (Aves) of Brazil. 44 records from Solanum_baretiae. 999 records from ZUEC-HEM - Coleção de Hemiptera do Museu de Zoologia da UNICAMP. 424 records from Colección de Reptiles del Instituto Alexander von Humboldt. 67 records from Stuart M. Fullerton Collection of Arthropods (UCFC), University of Central Florida. 357 records from The avian collection at the Natural History Museum, Oslo, Norway. 781 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 4407 records from A Distribution and Taxonomic Reference Dataset of Geranium (Geraniaceae) in the New World. 4373 records from Colección del Herbario de la Universidad Tecnológica del Chocó. 10 records from Pauropoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 2 records from On the female of Gypona reversa DeLong & Martinson, 1972, with emphasis on genital structures (Insecta: Hemiptera: Cicadellidae). 615 records from Colección de Aves Museo Universitario de la Universidad de Antioquia. 7344 records from Lyman Entomological Museum (LEMQ). 9 records from Inventario Herpetológico Pauto M, La Primavera, Yopal, Casanare. 945 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 4 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2012. 1349 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia. 91 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 456 records from Levantamento de Arbóreas do Parque Nacional do Jaú. 71 records from Colección de Referencia de Peces del Museo de Ciencias de la Universidad El Bosque. 971 records from Mamíferos de la colección del Instituto Alexander von Humboldt. 6 records from Alobevania, a new genus of neotropical ensign wasps (Hymenoptera: Evaniidae), with three new species: integrating taxonomy with the World Wide Web.. 516 records from NCSM Fishes Collection. 364 records from Colección Herpetológica de la Patagonia. 84 records from Colección de Referencia de Equinodermos del Museo de Ciencias de la Universidad El Bosque. 44 records from AM: Freshwater Invertebrates (1900-2005). 1621 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 3 records from Myoglanis aspredinoides (Siluriformes: Heptapteridae), a new catfish from the Río Ventuari, Venezuela.. 103 records from The South American annual killifish genus Austrolebias (Teleostei: Cyprinodontiformes: Rivulidae): phylogenetic relationships, descriptive morphology and taxonomic revision.. 745 records from (Table 2) Benthic foraminifers at DSDP Hole 72-518. 2394 records from Colección Científica de Referencia Zoológica del Chocó- Herpetología. 1408 records from (Table 2) Distribution of Campanian-Maestrichtian agglutinated foraminifers in DSDP Hole 78-543A. 2782 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Taminango, Nariño. 4248 records from Amphibian Specimens. 152539 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 4498 records from Colección Herbario Universidad Católica de Oriente. 1 records from Culture Collection of Cryophilic Algae. 96 records from Coleção de Nematoda do Museu Nacional - UFRJ. 6 records from On a new species of the genus Moenkhausia Eigenmann (Ostariophysi: Characidae).. 2 records from Plateurytion roigi sp. nov., a new geophilid centipede (Myriapoda: Chilopoda: Geophilomorpha) from Southern Chile. 32 records from Fundación Miguel Lillo - Colección Invertebrados. 487 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 964 records from Arachnida del Museo de Entomología de la Universidad del Valle. 20 records from The Scorpiones collection (RS) of the Muséum national d'Histoire naturelle (MNHN - Paris). 6 records from First occurrence of Nemobiinae crickets in the Lesser Antilles (Orthoptera, Grylloidea, Trigonidiidae), with the descriptions of three new species. 911 records from DMNS Bird Collection (Arctos). 2 records from Ituglanis paraguassuensis sp. n. (Teleostei: Siluriformes: Trichomycteridae): a new catfish from the rio Paraguacu, northeastern Brazil.. 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 968 records from The Fish Collection at the Zoologische Staatssammlung München. 880 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 12789 records from University of Florida Vertebrate Paleontology. 30 records from Naturalis Biodiversity Center (NL) - Odonata. 43 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 1 records from BioAcoustica: Wildlife Sounds Database. 7 records from A new species of Moenkhausia Eigenmann, 1903 (Characiformes: Characidae) from Amazon basin, Brazil. 3 records from Sipuncula collection of National Museum of Nature and Science. 6222 records from Museu Paraense Emilio Goeldi Herbarium. 2 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Aves Nidos (MFA-ZV-Or-N). 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 1890 records from Coleção de Echinodermata do Museu Nacional - MNRJ-ECHINO. 175 records from Monitoreo biológico en la cuenca Jamundí - Subcuenca Pance Campaña ARA - RARE - CVC – Asociación Calidris. 76 records from (Appendix A2) Calcareous nannofossil counts of ODP Site 207-1260. 2 records from Schizomida Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 7312 records from HBRA - Herbário do Instituto de Estudos Costeiros da Universidade Federal do Pará. 2994 records from CESJ - Herbário Leopoldo Krieger. 583 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-847B. 547 records from OUPR - Herbário "Professor José Badini". 3461 records from Global compendium of Aedes albopictus occurrence. 342 records from El efecto de la variación ambiental en la diversificación de anfibios y la prevalencia de su patógeno mortal: Un transecto por los humedales desde el Magdalena Medio hasta la Orinoquía. 1618 records from The Lepidoptera collection (EL) of the Muséum national d'Histoire naturelle (MNHN - Paris). 14 records from A review of the genus Orionis Shaw (Hymenoptera: Braconidae: Euphorinae) and first records of the genus from South America and the Oriental Region. 58 records from Mamíferos laguna El Tinije. 1764 records from Aves Playeras y Otras Aves Asociadas a Arrozales en los Departamentos de Casanare y Meta en 2009 - 2010. 2794 records from HAS-Algae - Coleção Ficológica do HAS. 1581 records from Colección Ornitológica de la Universidad Industrial de Santander. 77 records from Plantas alimenticias incluidas en la dieta local en el municipio de Montería, Córdoba. 10 records from Three new species and redescription of the type species of Soesilarishius Makhan, 2007 (Araneae: Salticidae: Euophryini). 25860 records from Colección Nacional de Aracnología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 5121 records from HAMAB - Herbário Amapaense. 1 records from A new species of Pelecium Kirby (Coleoptera: Carabidae: Peleciini) from the Atlantic Forest biome, Brazil. 6 records from CUMV Mammal Collection (Arctos). 117 records from CMC Cincinnati Museum Center Invertebrate Paleontology. 1072 records from CUMV Fish Collection (Arctos). 6432 records from Field Museum of Natural History (Zoology) Bird Collection. 86506 records from Plantae of Costa Rica (INBio). 10254 records from Inventario de fauna presente en la jurisdicción de Corantioquia. 3 records from Mycology herbarium, Tromsø Museum. 10168 records from Estudios bióticos: Plantas, edafofauna epígea, anfibios y aves en el complejo de páramos Cruz Verde - Sumapaz. 99 records from UAM Mammal Collection (Arctos). 5 records from IZIKO: Marine Invertebrate Collection (1900-2011). 7 records from A new species of Hemigrammus Gill, 1858 (Characiformes: Characidae) from Rio Caura, Venezuela.. 158 records from Biodiversidad del Phyllum Mollusca asociada a las plataformas de explotación de gas natural (Campo Chuchupa: La Guajira, Colombia). 51 records from Revision of Archaeoteleia Masner (Hymenoptera: Platygastroidea, Scelionidae).. 2 records from Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil.. 2 records from Collection des Mollusques (BOUM). 26519 records from Reef Life Survey: Global reef fish dataset. 1 records from MfN - Micropaleontology. 5 records from The mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1960 records from Colección de Algas del Herbario Nacional, Museo Nacional de Historia Natural de Chile. 834 records from Museum Victoria provider for OZCAM. 1504 records from University of Amsterdam (NL) - Páramo vegetation research, Western Andean Cordillera. 1 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 2303 records from (Appendix) Dinoflagellate abundance in ODP Site 202-1233. 759 records from Herbario Nacional de Plantas Celulares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 11519 records from MBM - Herbário do Museu Botânico Municipal. 314 records from Peces laguna El Tinije. 6707 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 1833 records from (Appendix) Benthic foraminifera distribution of upper Creatceous and Paleocene at DSDP Hole 72-516F. 27 records from Coleção de Nemertea do Museu Nacional - UFRJ. 3596 records from Harvestmen of French Guiana. 102030 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 5 records from New species of Curculionichthys (Siluriformes: Loricariidae) from the eastern Guiana Shield. 12 records from Ohio State University Tetrapod Division - Amphibian Collection (OSUM). 1592 records from Herbario Museo de La Salle Bogotá (MLS). 14328 records from ZUEC-POL - Coleção de Polychaeta do Museu de Zoologia da UNICAMP. 1662 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campañas 2009-2010. 10 records from Five new species and a new country record in American Cerambycidae (Coleoptera). 2867 records from Tree Diversity and Dynamics of the Forest of Seu Nico (Brazil/MG). 717912 records from Insecta of Costa Rica (INBio). 28570 records from Escarabajos Coprófagos (Coleoptera: Scarabaeinae) de la Colección Entomológica del Instituto Alexander von Humboldt. 202 records from Inventario de Aves Buenos Aires, Tauramena, Casanare. 4430 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 223 records from Gothenburg Herbarium - Types (GBIF:IH:GB:Herbarium). 975 records from (Appendix B) Dinoflagellate cysts in Southeast Pacific Ocean surface sediments. 2 records from First record of order Embioptera (Insecta) for the State of Tocantins, Brazil, with description of a new species of Clothoda Enderlein. 21572 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Guantiva - La Rusia. 24 records from BMSM Bailey-Matthews National Shell Museum. 45786 records from Field Museum of Natural History (Zoology) Mammal Collection. 13 records from Bolivian Mimosa (Leguminosae, Mimosoideae): three new species and a species checklist. 1 records from Ichthyologie ZMK. 2 records from MVZ Hildebrand Collection (Arctos). 51 records from Packer Collection / Xenochilicola bees, Chile. 40 records from Lund Museum of Zoology (MZLU). 15009 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 62 records from Myriapoda of Costa Rica (INBio). 367416 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 1 records from Reptilia ZMK. 450 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 747 records from FCAB - Herbário Friburguense. 1 records from Crustacea ZMK. 6 records from ZUEC-PLA - Coleção de Platyhelmintes do Museu de Zoologia da UNICAMP. 2 records from Catalogue of the family Ologamasidae Ryke (Acari: Mesostigmata). 480 records from CAS Invertebrate Zoology (IZ). 2 records from A new species of the genus Rhinoleucophenga (Diptera: Drosophilidae) and redescription of five species from Neotropical region. 10 records from Description of a new species of the genus Chaetostoma from the Orinoco River drainage with comments on Chaetostoma milesi Fowler, 1941 (Siluriformes: Loricariidae). 535 records from Crustacea collection of National Museum of Nature and Science. 2 records from Echinodermata ZMK. 3061 records from (Table 4) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-846B. 3 records from A new species of Anacroneuria Klapálek 1909 (Plecoptera: Perlidae) from Espírito Santo State, southeastern Brazil and comments on additional species. 7211 records from MBML-Aves - Coleção de Aves MBML. 513 records from Occurrences des observations de la campagne REMMOA Antilles (2008). 217 records from Succession of benthic hard-bottom communities abundance at station Errina2012_MDD7. 203 records from Tallinn Botanic Garden. 2 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2010. 1379 records from Colección de Zoología Invertebrados - Otros invertebrados. 24 records from UCM Bird Eggs/Nests Collection (Arctos). 8144 records from Herbarium areqvipense (HUSA). 12 records from NCSM Birds Collection. 1000 records from Colección Limnológica del Chocó. 1376 records from Vertical distribution of nannofossils in the section of DSDP Site 72-516. 1299 records from UAM Bird Collection (Arctos). 829 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 3630 records from ZUEC-BIV - Coleção de Bivalvia do Museu de Zoologia da UNICAMP. 553 records from Composición florística y estructura de una parcela permanente en bosques humedos tropicales del resguardo Emberá Chontadural, municipio de Mutatá, Antioquia. 97 records from New distributional data on aquatic and semiaquatic bugs (Hemiptera: Heteroptera: Gerromorpha & Nepomorpha) from South America. 9 records from A new species of Margaromantis Piza, 1982 ( Insecta : Mantodea ) from Brazil. 42 records from arim. 232 records from Monitoreo biológicos en la cuenca Frayle, ARA - RARE - CVC – Asociación Calidris. 90077 records from Museum of Comparative Zoology, Harvard University. 63 records from Marine gastropod distribution from patagonian shallow waters. 84 records from Naturalis Biodiversity Center (NL) - Cnidaria. 5 records from The genera of the Neotropical armored catfish subfamily Loricariinae (Siluriformes: Loricariidae): a practical key and synopsis.. 8595 records from Australia's Virtual Herbarium. 13 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 36087 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 431 records from Plantas Bosque Seco Chicamocha. 1 records from New records of sabellids and serpulids (Polychaeta: Sabellidae, Serpulidae) from the Tropical Eastern Pacific. 33435 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 2 records from The cladorhizid fauna (Porifera, Poecilosclerida) of the Caribbean and adjacent waters. 27 records from Vascular Plant Herbarium, UiB. 490 records from Dinoflagellate cysts in western equatorial Atlantic surface sediments. 1406 records from Colección de mamíferos del Museo de Historia Natural de la Pontificia Universidad Javeriana. 1 records from Applying n-dimensional hypervolumes for species delimitation: unexpected molecular, morphological, and ecological diversity in the Leaf-Toed Gecko Phyllodactylus reissii Peters, 1862 (Squamata: Phyllodactylidae) from northern Peru. 35 records from Colección de Platyhelminthes del Museo Nacional de Historia Natural de Chile. 158 records from Scarabaeoidea y colección de tipos de la colección entomológica del Centro de Estudios en Zoología, Universidad de Guadalajara. 2 records from Kathryn Kalmbach Herbarium. 28600 records from Ichthyology Collection - Royal Ontario Museum. 18 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 1238 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 163 records from Entomofauna laguna El Tinije. 29 records from USGS PWRC - Native Bee Inventory and Monitoring Lab - US-CA-MX - Bees. 6004 records from Colección Limnológica Universidad de Antioquia. 164 records from CAS Ornithology (ORN). 5 records from A New Southern Caribbean Species of Angel Shark (Chondrichthyes, Squaliformes, Squatinidae), Including Phylogeny and Tempo of Diversification of American Species. 8697190 records from EOD - eBird Observation Dataset. 258 records from Cnidarios del proyecto Macrofauna Corpoguajira. 15 records from Mamíferos, aves y peces de la Isla Cayo Serrana durante la Expedición Seaflower 2016. 1 records from Aristathlus imperatorius Bergroth, a newly recognized synonym of Reduvius iopterus Perty, with the new combination Aristathlus iopterus (Perty, 1834) (Hemiptera: Reduviidae: Harpactorinae) ​. 8014 records from Primera caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 662 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 3002 records from Colección de Peces Universidad Católica de Oriente. 20797 records from iNaturalist Research-grade Observations. 16321 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 5506 records from Caracterización de flora, edafofauna epígea, anfibios y aves del complejo de Páramos de Sotará, Cauca. 1 records from National Taiwan University. 20 records from Revision of the Neotropical genus Macreupelmus Ashmead (Hymenoptera: Chalcidoidea: Eupelmidae). 102 records from UCBG TAPIR Provider. 1 records from Ohio State University Tetrapod Division - Reptile Collection (OSUM). 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 208 records from Global caridean shrimp fauna. 4 records from A new Mapinguari Papavero & Wilcox (Diptera, Mydidae, Mydinae) from Minas Gerais State, Brazil. 10936 records from Hymenoptera de la Colección Entomológica del Instituto Alexander von Humboldt. 3243 records from CONN. 4440 records from HUCS - Herbário da Universidade de Caxias do Sul. 1 records from A new shallow water species of Artemisina Vosmaer, 1885 (Microcionidae, Demospongiae; Porifera) from Northeastern Brazil. 5 records from Aranzadi Ringing Scheme (bird ring-recovery data). 3715 records from Registros biológicos de especies de plantas del Bosque Seco en Colombia presentes en el Herbario JBGP. 5 records from H.A. Stephens Herbarium. 86 records from (Table 1) Planktonic foraminifera counts and stable oxygen isotope ratios of Pacific Ocean surface sediments. 73 records from NYSM Birds. 1390 records from Caracterización de avifauna de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 2885 records from Recent Invertebrates Specimens. 8 records from First record of Neoempheria Osten Sacken (Diptera, Mycetophilidae) biology in the Neotropical region, with associations between its larvae and fungi. 1 records from Catalogue of the Teratomyzidae (Diptera, Opomyzoidea) of the World. 2209 records from UFRN-Fungos - Herbário UFRN - Fungos. 71 records from Spiders of French Guiana. 2874 records from Colección de Ofidios Museo de La Salle Bogotá (MLS). 3479 records from Coleção de Polychaeta do Museu Nacional. 65 records from Taxonomy of the catfish genus Pseudoplatystoma Bleeker (Siluriformes: Pimelodidae) with recognition of eight species.. 7485 records from Herbario CDMB - Jardín Botánico Eloy Valenzuela. 1 records from The water mite family Aturidae Thor (Acari: Hydrachnidia) from Ghana, with the description of twelve new species. 1 records from Two new species and new records of the genus Paraopisthosyllis Hartmann-Schröder, 1991 (Annelida: Syllidae) from northeastern Brazil and Philippine Islands. 2795 records from Invertebrates Collection of the Swedish Museum of Natural History. 91 records from KUBI Ichthyology Tissue Collection. 173 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Vascular Plants. 4 records from AM: Terrestrial Insect Collections (1896-2000). 1628 records from Global Lacustrine Diatoms. 780 records from Comportamiento espacio-temporal de la densidad fitoplanctónica en el año 2015 Magdalena, Colombia. 9206 records from Estonian Museum of Natural History. 603 records from Registros preliminares del "Catálogo de cangrejos ermitaños del mar Caribe colombiano". 2 records from Male sleeping aggregation of multiple Eucerini bee genera (Hymenoptera: Apidae) in Chapada Diamantina, Bahia, Brazil. 213 records from Catálogo electrónico de especímenes depositados en el Herbario de la Universidad de Texas en Austin, Fase IV. 2966 records from Bolivian Amazon lowland fish metacommunity data. 976 records from University of California Museum of Paleontology. 1 records from A new species of Oreodera Audinet-Serville, 1835 from Ecuador (Coleoptera, Cerambycidae, Lamiinae) and new geographical records. 4268 records from Free-living marine Nematodes from Ali, Rada Tilly and El Limite sandy beaches (Chubut, Argentina) 2006.. 5 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 2767 records from HFSL - Herbário Dr. Ary Tupinambá Penna Pinheiro. 8557 records from Mammals housed at MHNG, Geneva. 20 records from DMNS Marine Invertebrate Collection (Arctos). 89 records from Arvenses y árboles asociados a cafetales de Cundinamarca. 6 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Aves (MFA-ZV-Or). 1244 records from Mosquitoes_of_French_Guiana. 6 records from Las monocotiledóneas mexicanas, una sinopsis florística. 26065 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Arachnology National Collection (MACNAr).. 9 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 75036 records from ALCB - Herbário Alexandre Leal Costa. 28 records from Onychophora of Costa Rica (INBio). 152 records from Coleção de Platyhelminthes do Museu Nacional - UFRJ. 2372 records from HUSC - Herbário Unisanta. 14562 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 3 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 581 records from mel. 18 records from (Table 3) Foraminiferal species in DSDP Sample 78-541-5-3,19-21. 4 records from Thorectinae (Porifera: Demospongiae: Dictyoceratida) from Northeastern Brazil: two new species and transfer of Scalarispongia cincta (Boury-Esnault, 1973) to the genus Thorecta Lendenfeld, 1888. 1576 records from Estonian University of Life Sciences. 22817 records from Essig Museum of Entomology. 25267 records from CAS Ichthyology (ICH). 196 records from Colección Plantas Vasculares - Herbario del Departamento de Biología, Bioquímica y Farmacia de la Universidad Nacional del Sur. 1 records from A new species of Lathrolestes Förster (Hymenoptera: Ichneumonidae) from Peruvian Amazonia. 2 records from Trichomycterus pauciradiatus, a new catfish species from the upper rio Paraná basin, southeastern Brazil (Siluriformes: Trichomycteridae).. 1862 records from corrego_fazendinha-gallery-forest_v2. 13949 records from University of Amsterdam (NL) - Páramo Vegetation Research, Chingaza - Cruz Verde - Monserrate -Guasca, Colombia. 578 records from The Diatom Collection of Franz Josef Weinzierl at the Botanische Staatssammlung München. 8052 records from Estudios bióticos: Plantas, artropofauna edáfica, anfibios y aves del Complejo de Páramos Iguaque Merchán. 1678 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 1082 records from Colección de Saurios Museo de La Salle Bogotá (MLS). 1828 records from Colección de Anfibios Museo de La Salle Bogotá (MLS). 27 records from Tejidos de anfibios y reptiles de la ventana piloto Paz de Ariporo - Hato Corozal. 151 records from DMNS Mammal Collection (Arctos). 1340 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Santa Fé de Antioquia, Antioquia (primer censo). 247 records from Quirópteros Asociados al Bosque Seco de la Vereda El Carbonero, Santander de Quilichao, Cauca. 214 records from Fiocruz/COLTRYP - Coleção de Trypanosoma de Mamíferos Silvestres, Domésticos e Vetores. 20 records from Cyatta abscondita: Taxonomy, Evolution, and Natural History of a New Fungus-Farming Ant Genus from Brazil. 6 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2011. 725 records from Southern right whales distribution in Bahía Nueva, Puerto Madryn, Argentina. 3 records from Achaeta becki sp. nov. (Oligochaeta: Enchytraeidae) from Amazonian forest soils. 129 records from Angelo State Natural History Collections (ASNHC) - Ornithology Collection. 2444 records from TNHC Ichthyology Collection. 34 records from Mammal collection, Natural History Museum, University of Oslo. 52 records from Caracterización vegetal de una zona de alta montaña (litoral de San Juan) como herramienta de proyección para el establecimiento de una figura de conservación en el chocó biogeográfico. 6273 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 106 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 11 records from Desarrollar las actividades tendientes al manejo, conocimiento y conservación del Comino crespo (Aniba perutilis hemsl.), formuladas en el plan de conservación para la especie en el departamento del Meta. 355 records from Carábidos (Coleoptera: Carabidae) del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 7 records from A new and endangered species of Kingsleya Ortmann, 1897 (Crustacea: Decapoda: Brachyura: Pseudothelphusidae) from Ceará, northeastern Brazil. 3 records from Anatomical investigation of the slender catshark Schroederichthys tenuis Springer, 1966, with notes on intrageneric relationships (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 16 records from University of British Columbia Herbarium (UBC) - Lichen Collection. 568 records from MVZ Bird Observations (Arctos). 2 records from Tanypus urszulae, a new Tanypodinae (Diptera: Chironomidae) from the Neotropical Region. 4114 records from Cruzando el Caribe - Construyendo la capacidad para el ecoturismo en el Darién y Urabá. 11645 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 2214 records from A checklist to the wasps of Peru (Hymenoptera, Aculeata). 277 records from Colección de Entomología - Auchenorrhyncha. 3 records from Rivulus sape, a new species of killifish (Cyprinodontiformes: Rivulidae) from the Paragua River system, Caroní River drainage, Guyana Shield, Venezuela.. 33 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 6325 records from Colección Entomológica de la Universidad de Antioquia. 2484 records from NX - Herbário Nova Xavantina. 1 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 5477 records from Colección de mamíferos de la Universidad del Valle. 191 records from NRM-Herpetology. 763 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Cryptogamic National Collection (BAc).. 323 records from Seaweeds records from Argentina and Uruguay. 571 records from LUSC - Herbário de Lages da Universidade do Estado de Santa Catarina. 29 records from Abundance of Globorotalia menardii of sediment core GeoB2821-1. 22 records from Abundance of Globorotalia menardii of sediment core GeoB2822-2. 14 records from Abundance of Globorotalia menardii of sediment core GeoB2110-3. 2 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 1040 records from Anfibios y Reptiles reportados en humedales del departamento de Córdoba. 83 records from Total foraminifera counts from M35/1_MSN1043. 233 records from Total foraminifera counts from M35/1_MSN1044. 43 records from Total foraminifera counts from M35/1_MSN1045. 134 records from Total foraminifera counts from M35/1_MSN1046. 198 records from Total foraminifera counts from M35/1_MSN1047. 97 records from Total foraminifera counts from M35/1_MSN1048. 79 records from Total foraminifera counts from M35/1_MSN1049. 126 records from Total foraminifera counts from M35/1_MSN1050. 84 records from Total foraminifera counts from M35/1_MSN1051. 49 records from Total foraminifera counts from M35/1_MSN1052. 33 records from Total foraminifera counts from M35/1_MSN1053. 62 records from Total foraminifera counts from M35/1_MSN1054. 79 records from Total foraminifera counts from M35/1_MSN1055. 67 records from Total foraminifera counts from M35/1_MSN1056. 54 records from Total foraminifera counts from M35/1_MSN1057. 52 records from Total foraminifera counts from M35/1_MSN1058. 66 records from Total foraminifera counts from M35/1_MSN1059. 118 records from Total foraminifera counts from M35/1_MSN1060. 97 records from Total foraminifera counts from M35/1_MSN1061. 80 records from Total foraminifera counts from M35/1_MSN1062. 60 records from Total foraminifera counts from M35/1_MSN1063. 66 records from Total foraminifera counts from M35/1_MSN1064. 85 records from Total foraminifera counts from M35/1_MSN1065. 98 records from Total foraminifera counts from M35/1_MSN1067. 130 records from Total foraminifera counts from M35/1_MSN1068. 157 records from Total foraminifera counts from M35/1_MSN1069. 108 records from Total foraminifera counts from M35/1_MSN1070. 125 records from Plasm bearing foraminifera counts from M35/1_MSN1043. 94 records from Plasm bearing foraminifera counts from M35/1_MSN1044. 87 records from Plasm bearing foraminifera counts from M35/1_MSN1045. 149 records from Plasm bearing foraminifera counts from M35/1_MSN1046. 50 records from Plasm bearing foraminifera counts from M35/1_MSN1047. 169 records from Plasm bearing foraminifera counts from M35/1_MSN1048. 87 records from Plasm bearing foraminifera counts from M35/1_MSN1049. 82 records from Plasm bearing foraminifera counts from M35/1_MSN1050. 77 records from Plasm bearing foraminifera counts from M35/1_MSN1051. 26 records from Plasm bearing foraminifera counts from M35/1_MSN1052. 209 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (forofitos). 85 records from Plasm bearing foraminifera counts from M35/1_MSN1053. 67 records from Plasm bearing foraminifera counts from M35/1_MSN1054. 5 records from Plasm bearing foraminifera counts from M35/1_MSN1055. 84 records from Plasm bearing foraminifera counts from M35/1_MSN1056. 40 records from Plasm bearing foraminifera counts from M35/1_MSN1057. 53 records from Plasm bearing foraminifera counts from M35/1_MSN1058. 70 records from Plasm bearing foraminifera counts from M35/1_MSN1059. 120 records from Plasm bearing foraminifera counts from M35/1_MSN1060. 86 records from Plasm bearing foraminifera counts from M35/1_MSN1061. 113 records from Plasm bearing foraminifera counts from M35/1_MSN1062. 64 records from Plasm bearing foraminifera counts from M35/1_MSN1063. 164 records from Plasm bearing foraminifera counts from M35/1_MSN1064. 108 records from Plasm bearing foraminifera counts from M35/1_MSN1065. 196 records from Plasm bearing foraminifera counts from M35/1_MSN1067. 160 records from Plasm bearing foraminifera counts from M35/1_MSN1068. 90 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 200 records from Plasm bearing foraminifera counts from M35/1_MSN1070. 1734 records from Aves Marinas y Playeras en el PNN Sanquianga y la Bocana de Iscuandé entre 2007 y 2009. 3215 records from Diveboard - Scuba diving citizen science observations. 113 records from Bryophyte herbarium, NTNU University Museum. 3795 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 12 records from Succession of benthic hard-bottom communities abundance at Liliguapi in 2011. 281 records from Diplopoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 38315 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Herpetology National Collection (MACNHe).. 13664 records from Illinois Natural History Survey Insect Collection. 1959 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Vascular Plants National Collection (BAv).. 4 records from Sea Education Association Sargasso Sea Cruise C247 May 2013. 105 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 2603 records from VIC - Herbário da Universidade Federal de Viçosa. 2827 records from The Brown University Foraminiferal Data Base (BFD). 12 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5110-4. 36 records from Sedimentological investigation on core V15-168. 39 records from Sedimentological investigation on core V25-56. 60 records from Sedimentological investigation on core V25-76. 10 records from Content of coarse fraction and G. menardii in sediment corev V15-169. 37 records from Content of coarse fraction and G. menardii in sediment corev V16-202. 11 records from Content of coarse fraction and G. menardii in sediment corev V25-39. 26 records from Content of coarse fraction and G. menardii in sediment corev V25-42. 24 records from Content of coarse fraction and G. menardii in sediment corev V25-43. 22 records from Content of coarse fraction and G. menardii in sediment corev V25-47. 6 records from Content of coarse fraction and G. menardii in sediment corev V25-48. 13 records from Content of coarse fraction and G. menardii in sediment corev V25-49. 13 records from Content of coarse fraction and G. menardii in sediment corev V25-52. 18 records from Content of coarse fraction and G. menardii in sediment corev V25-57. 31 records from Content of coarse fraction and G. menardii in sediment corev V25-63. 6 records from Content of coarse fraction and G. menardii in sediment corev V25-64. 9 records from Content of coarse fraction and G. menardii in sediment corev V25-65. 29 records from Content of coarse fraction and G. menardii in sediment corev V26-101. 107 records from Content of coarse fraction and G. menardii in sediment corev V26-102. 8 records from Content of G. menardii in sediment core V25-69. 35 records from ZUEC-NEM - Coleção de Nemertea do Museu de Zoologia da UNICAMP. 7 records from Content of G. menardii in sediment core V25-70. 785 records from Faunal distribution of the most important planktic foraminiferal species in the investigated surface sediment samples from the Chilean continental slope between 23°S and 44°S. 1156 records from Colección Entomológica de la Universidad Tecnológica del Chocó. 59 records from New species and new records of Cumacea (Crustacea: Peracarida: Cumacea) from mesophotic reefs of Puerto Rico and U. S. Virgin Islands, Caribbean Sea. 7 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 83 records from Colección preservada Jardín Botánico de la Patagonia Extraandina. 21 records from Phytoplankton abundance at the sea bottom off Sechura in january 2007, Peru. 426 records from Dinoflagellate assemblage in surface sediments of the South Atlantic. 151 records from (Appendix A) Abundance of calcareous dinoflagellates of sediment core GeoB2204-2. 14 records from Succession of benthic hard-bottom communities abundance at Liliguapi in 2012. 517 records from (Appendix B Table 2) Abundance of organic-walled dinoflagellate cysts of sediment core GeoB2204-2. 8 records from Review of the ant genus Rogeria (Hymenoptera: Formicidae) in Guyana.. 2104 records from Colección Ictiológica del CENPAT-CONICET. 1040 records from Dinoflagellate cyst counts of sediment core M35003-4. 486 records from Dinoflagellates of sediment core GeoB1523-1. 140 records from Dinoflagellate cysts counted on two fractions of surface sediment samples from stations A-9 to A-39. 46 records from Phytoplankton counted on two fractions of surface sediment samples from stations B-5 to B-47. 78 records from Phytoplankton counted on two fractions of surface sediment samples from Meteor stations M35003-4 to M35010-3. 204 records from Dinoflagellates (organic) in surface sediments of the South Atlantic. 706 records from (Table 1) Benthic foraminifera at DSDP Site 72-516. 9 records from (Fig. 3) Pollen analysis of the Bosque de Avicennia core. 1 records from (Fig. 4) Pollen analysis of the Campo Salgado core. 2 records from (Fig. 5) Pollen analysis of the Furo do Chato core. 2 records from Benthic hard-bottom communities abundance at Lilliguapy in 2010. 93 records from Dinoflagellate cysts in surface sediment samples of Meteor cruises M20/2, M23/1, M34/1, M34/2, M34/3 and M34/4. 18956 records from naturgucker. 20 records from Institut Botanic de Barcelona (IBB-CSIC-ICUB), BC-Lichen. 9 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 210 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 3468 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-158-1. 1301 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-159-1. 2268 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-173-3. 938 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-175-1. 267 records from ZUEC-CRU - Coleção de Crustacea do Museu de Zoologia da UNICAMP. 1961 records from Herbario Nacional de Plantas Vasculares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 5573 records from Estudios bióticos: plantas, edafofauna epígea, anfibios y aves en los complejos de páramos los Nevados y Chilí-Barragán. 693 records from The First Comprehensive Description of the Biodiversity and Biogeography of Antarctic and Sub-Antarctic Intertidal Communities. 450 records from Johnson & Cora, Hymenoptera Online (HOL). 599 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Chavez 2011. 23 records from Erik Acharius lichen collection. 8 records from Mean values of fractionated primary production and protozoan abundance from the photic layer collected at 50 m depth in Mejillones Bay. 11 records from Phytoplankton abundance in surface water in 1992, Ancon, Peru. 12 records from Phytoplankton abundance in surface water in 1993, Ancon, Peru. 14 records from Phytoplankton abundance in surface water in 1994, Ancon, Peru. 18 records from Phytoplankton abundance in surface water in 1995, Ancon, Peru. 17 records from Phytoplankton abundance in surface water in 1996, Ancon, Peru. 26 records from Phytoplankton abundance in surface water in 1997, Ancon, Peru. 33 records from Phytoplankton abundance in surface water in 1998, Ancon, Peru. 27 records from Phytoplankton abundance in surface water in 1999, Ancon, Peru. 36 records from Phytoplankton abundance in surface water in 2000, Ancon, Peru. 30 records from Phytoplankton abundance in surface water in 2001, Ancon, Peru. 33 records from Phytoplankton abundance in surface water in 2002, Ancon, Peru. 16 records from Phytoplankton abundance in surface water in 2003, Ancon, Peru. 12 records from Phytoplankton abundance in surface water in 2004, Ancon, Peru. 6 records from Phytoplankton abundance in surface water in 2005, Ancon, Peru. 79 records from Phytoplankton abundance at station Sechin_EP1 in 2002, Casma, Peru. 118 records from Phytoplankton abundance at Station Sechin_EP2 in 2002, Casma, Peru. 50 records from Phytoplankton abundance at several stations in December 2004, Chipana, Chile. 73 records from Phytoplankton abundance at several stations in January 2005, Chipana, Chile. 16 records from Phytoplankton abundance at station Rigel_1_2005-02 in Febraury 2005, Chipana, Chile. 17 records from Phytoplankton abundance at station Rigel_2_2005-02 in Febraury 2005, Chipana, Chile. 17 records from Phytoplankton abundance at station Rigel_3_2005-02 in Febraury 2005, Chipana, Chile. 10 records from Phytoplankton abundance at station Rigel_4_2005-02 in Febraury 2005, Chipana, Chile. 10 records from Phytoplankton abundance at station Rigel_5_2005-02 in Febraury 2005, Chipana, Chile. 10 records from Phytoplankton abundance at station Rigel_6_2005-02 in Febraury 2005, Chipana, Chile. 6 records from Phytoplankton abundance at station Rigel_1_2005-03 in March 2005, Chipana, Chile. 11 records from Phytoplankton abundance at station Rigel_2_2005-03 in March 2005, Chipana, Chile. 10 records from Phytoplankton abundance at station Rigel_3_2005-03 in March 2005, Chipana, Chile. 11 records from Phytoplankton abundance at station Rigel_4_2005-03 in March 2005, Chipana, Chile. 10 records from Phytoplankton abundance at station Rigel_5_2005-03 in March 2005, Chipana, Chile. 8 records from Phytoplankton abundance at station Rigel_6_2005-03 in March 2005, Chipana, Chile. 22 records from Phytoplankton abundance at station Rigel_1_2005-04 in April 2005, Chipana, Chile. 28 records from Phytoplankton abundance at station Rigel_2_2005-04 in April 2005, Chipana, Chile. 15 records from Phytoplankton abundance at station Rigel_3_2005-04 in April 2005, Chipana, Chile. 18 records from Phytoplankton abundance at station Rigel_4_2005-04 in April 2005, Chipana, Chile. 23 records from Phytoplankton abundance at station Rigel_5_2005-04 in April 2005, Chipana, Chile. 18 records from Phytoplankton abundance at station Rigel_6_2005-04 in April 2005, Chipana, Chile. 23 records from Phytoplankton abundance at station Rigel_1_2005-05 in May 2005, Chipana, Chile. 29 records from Phytoplankton abundance at station Rigel_2_2005-05 in May 2005, Chipana, Chile. 27 records from Phytoplankton abundance at station Rigel_3_2005-05 in May 2005, Chipana, Chile. 15 records from Phytoplankton abundance at station Rigel_4_2005-05 in May 2005, Chipana, Chile. 32 records from Phytoplankton abundance at station Rigel_5_2005-05 in May 2005, Chipana, Chile. 22 records from Phytoplankton abundance at station Rigel_6_2005-05 in May 2005, Chipana, Chile. 4 records from Phytoplankton abundance at station Rigel_1_2005-07 in July 2005, Chipana, Chile. 3 records from Phytoplankton abundance at station Rigel_2_2005-07 in July 2005, Chipana, Chile. 7 records from Phytoplankton abundance at station Rigel_4_2005-07 in July 2005, Chipana, Chile. 4 records from Phytoplankton abundance at station Rigel_6_2005-07 in July 2005, Chipana, Chile. 3 records from Phytoplankton abundance at station Rigel_2_2005-08 in August 2005, Chipana, Chile. 1 records from Phytoplankton abundance at station Rigel_3_2005-08 in August 2005, Chipana, Chile. 2997 records from Colección Macroinvertebrados Acuáticos Universidad Católica de Oriente. 3 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 4 records from Phytoplankton abundance at station Rigel_5_2005-08 in August 2005, Chipana, Chile. 5 records from Phytoplankton abundance at station Rigel_6_2005-08 in August 2005, Chipana, Chile. 8 records from Phytoplankton abundance at station Casma_2003-01-07_2, Casma, Peru. 9 records from Phytoplankton abundance at station Casma_2003-01-30_1, Casma, Peru. 7 records from Phytoplankton abundance at station Casma_2003-02-15_2, Casma, Peru. 8 records from Phytoplankton abundance at station Casma_2003-02-27_1, Casma, Peru. 13 records from Phytoplankton abundance at station Casma_2003-03-27_2, Casma, Peru. 12 records from Phytoplankton abundance at station Casma_2003-04-14_1, Casma, Peru. 6 records from Phytoplankton abundance at station Casma_2003-04-28_1, Casma, Peru. 9 records from Phytoplankton abundance at station Casma_2003-01-07_1, Casma, Peru. 8 records from Phytoplankton abundance at station Casma_2003-01-30_2, Casma, Peru. 1 records from Porifera MZS. 9 records from Phytoplankton abundance at station Casma_2003-02-15_1, Casma, Peru. 7 records from Phytoplankton abundance at station Casma_2003-02-27_2, Casma, Peru. 11 records from Phytoplankton abundance at station Casma_2003-03-13_1, Casma, Peru. 9 records from Phytoplankton abundance at station Casma_2003-03-13_2, Casma, Peru. 16 records from Phytoplankton abundance at station Casma_2003-03-27_1, Casma, Peru. 1125 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn).. 10 records from Phytoplankton abundance at station Casma_2003-04-14_2, Casma, Peru. 381 records from CAS Mammalogy (MAM). 7 records from Phytoplankton abundance at station Casma_2003-04-28_2, Casma, Peru. 9 records from Phytoplankton abundance at station Casma_2003-06-04_2, Casma, Peru. 8 records from Phytoplankton abundance at station Casma_2003-06-24_1, Casma, Peru. 5 records from Phytoplankton abundance at station Casma_2003-06-24_2, Casma, Peru. 9994 records from UMMZ Mammal Collection. 11 records from Phytoplankton abundance at station Sechin_2003-07-15_1, Casma, Peru. 10 records from Phytoplankton abundance at station Sechin_2003-07-15_2, Casma, Peru. 11 records from Phytoplankton abundance at station Sechin_2003-08-06_1, Casma, Peru. 10 records from Phytoplankton abundance at station Sechin_2003-08-06_2, Casma, Peru. 13 records from Phytoplankton abundance at station Sechin_2003-08-27_1, Casma, Peru. 11 records from Phytoplankton abundance at station Sechin_2003-08-27_2, Casma, Peru. 14 records from Phytoplankton abundance at station Sechin_2003-09-18_1, Casma, Peru. 12 records from Phytoplankton abundance at station Sechin_2003-09-18_2, Casma, Peru. 11 records from Phytoplankton abundance at station Sechin_2003-10-03_1, Casma, Peru. 16 records from Phytoplankton abundance at station Sechin_2003-10-03_2, Casma, Peru. 1 records from Revision of southern African species of the anglerfish genus Chaunax (Lophiiformes: Chaunacidae), with descriptions of three new species. 20 records from Phytoplankton abundance at station Sechin_2003-10-22_1, Casma, Peru. 17 records from Phytoplankton abundance at station Sechin_2003-10-22_2, Casma, Peru. 10 records from Phytoplankton abundance at station Sechin_2003-11-06_1, Casma, Peru. 11 records from Phytoplankton abundance at station Sechin_2003-11-06_2, Casma, Peru. 21 records from Phytoplankton abundance at station Sechin_2003-11-25_1, Casma, Peru. 25 records from Phytoplankton abundance at station Sechin_2003-11-25_2, Casma, Peru. 16 records from Phytoplankton abundance at station Sechin_2003-12-03_1, Casma, Peru. 9 records from Phytoplankton abundance at station Sechin_2003-12-10_1, Casma, Peru. 15 records from Phytoplankton abundance at station Sechin_2003-12-10_2, Casma, Peru. 10 records from Phytoplankton abundance at station Sechin_2003-12-17_1, Casma, Peru. 10 records from Phytoplankton abundance at station Sechin_2003-12-17_2, Casma, Peru. 13750 records from Estudios bióticos: Plantas, anfibios, mamíferos, aves y edafofauna epígea (coleópteros y arácnidos), en el complejo de páramo Los Nevados. 14 records from Phytoplankton abundance at station Sechin_2003-12-28_1, Casma, Peru. 25 records from Phytoplankton abundance at station Sechin_2003-12-28_2, Casma, Peru. 11 records from Phytoplankton abundance at stations off Paita in August 1995, Piura, Peru. 21 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 10211 records from El Censo Neotropical de Aves Acuáticas en Colombia (CNAA): 2002 - 2011. 22 records from Phytoplankton abundance in surface water in January 2007, Sechura Bay, Peru. 20 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 45 records from Scratching the surface? Taxonomic revision of the subgenus Schizoptera (Odontorhagus) reveals vast undocumented biodiversity in the largest litter bug genus Schizoptera Fieber (Hemiptera: Dipsocoromorpha). 1138 records from Primera caracterización biológica de hormigas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 108 records from Rye, Barley, Oats Genetic Resources. N.I.Vavilov Research Institute of Plant Industry, St. Petersburg. 723 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña noviembre 2008. 497 records from Especies de Leptohyphes (Insecta: Ephemeroptera: Leptohyphidae) del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 18 records from The Crematogaster (Hymenoptera, Formicidae, Myrmicinae) of Costa Rica.. 45 records from (Table S2) Age determination of ODP Sites 202-1234 and 202-1235. 7663 records from University of Amsterdam (NL) - Páramo Vegetation Research, Rabanal, Guerrero and Villa de Leyva paramo complex, Colombia. 44 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2007. 281 records from (Table 2) Planktic foraminifera and their diversity indices of sediment surface samples from the Atlantic Ocean. 166 records from R-Criptogamos - Herbário do Museu Nacional - Criptogamos. 2585 records from Colección de Plantas Vasculares del Herbario Forestal UDBC "Gilberto Emilio Mahecha Vega". 6387 records from Registros biológicos del género Piper en el herbario HUA. 54 records from (Table 2) Absolute abundance of Contusotruncana contusa in DSDP Hole 39-356. 84 records from (Table 2) Absolute abundance of Contusotruncana contusa in DSDP Hole 72-516F. 12 records from (Table 3) Contusotruncana contusa morphotypes in DSDP Hole 39-356. 10 records from (Table 3) Contusotruncana contusa morphotypes in DSDP Hole 72-516F. 144 records from Anfibios y Reptiles Bosque Seco Chicamocha. 82 records from (Table 6) Distribution of live benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 1. 292 records from (Table A1) Calcareous nannofossil of the Middle Cenomanian Event in ODP Site 207-1260. 918 records from (Table 4) Occurrence of benthic foraminifera in samples from DSDP Hole 72-518. 1351 records from (Table 1) Distribution of planktonic foraminifera from samples spanning the Cretaceous-Tertiary boundary at ODP Hole 207-1259C. 107 records from Royal Ontario Museum - Entomology (ROME). 163 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac. 9 records from Museu de Ciències Naturals de Barcelona: MCNB-ZG. 2961 records from Tissues Specimens. 49 records from MfN - Fossil invertebrates Ia. 4 records from MfN - Fossil vertebrates III. 1 records from MfN - Trace fossils. 678 records from MfN - Fossil vertebrates IV. 4 records from MfN - Fossil plants (Cenophytic). 781 records from MfN - Fossil plants (Mesophytic). 27 records from MfN - Fossil plants (Paleophytic). 113 records from Nannofossil assemblage in surface sediments. 5 records from Relative abundance of radiolaria in surface sediments. 128 records from (Fig. 6, 7) Aragonite preservation of sediment core GeoB2204-2. 161 records from Coccolithophorids in surface sediments of the South Atlantic. 63 records from ZFMK DORSA. 2 records from A review of the families and genera of the superfamily PLATYSCELOIDEA Bowman & Gruner, 1973 (Crustacea: Amphipoda: Hyperiidea), together with keys to the families, genera and species. 48 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Ichthyology National Collection (MACNIct). 81 records from Coccolith percentage of surface sediment samples. 533 records from Coccolith percentage exclusive Emiliania huxleyi of surface sediment samples. 32 records from (Fig. 5b) Limacina dissolution index of sediment core GeoB2204-1. 30 records from (Fig. 5a) Limacina dissolution index of sediment core GeoB2205-4. 24 records from (Fig. 5c) Limacina dissolution index of sediment core GeoB2207-2. 4347 records from Aves Acuáticas en el Caribe Colombiano Entre 2007 y 2009. 4 records from Nannofossil abundance of Hole 15-146A. 322 records from Nannofossil abundance of Hole 15-147. 19 records from Nannofossil abundance of Hole 15-147C. 451 records from Nannofossil abundance of Hole 15-148. 95 records from Nannofossil abundance of Hole 15-149. 9 records from Nannofossil abundance of Hole 15-150. 11 records from Nannofossil abundance of Hole 15-153. 47 records from Nannofossil abundance of Hole 15-154. 225 records from Nannofossil abundance of Hole 15-154A. 127 records from Nannofossil abundance of Hole 78-541. 12 records from Nannofossil abundance of Hole 78-542. 10936 records from Hymenoptera de la Colección Entomológica del Instituto Alexander von Humboldt. 2 records from Nannofossil abundance of Hole 78-542A. 35 records from Nannofossil abundance of Hole 78-543. 5 records from Nannofossil abundance of Hole 34-320A. 2 records from Nannofossil abundance of Hole 34-321. 1 records from Benthic hard-bottom communities abundance at Lilliguapy in 2011. 28 records from Nannofossil abundance of Hole 16-155. 4 records from Nannofossil abundance of Hole 16-156. 5 records from Nannofossil abundance of Hole 3-22. 4 records from Nannofossil abundance of Hole 4-23. 10 records from Nannofossil abundance of Hole 4-25. 4 records from Nannofossil abundance of Hole 4-29. 6 records from Nannofossil abundance of Hole 4-30. 4 records from Nannofossil abundance of Hole 4-31. 435 records from Community dynamics in a species-rich patch in the Brazilian Atlantic Forest near Viçosa/MG. 34 records from Nannofossil abundance of Hole 9-84. 88 records from Microfossil abundance of Hole 16-157. 8 records from Microfossil abundance of Hole 16-157A. 97 records from Microfossil abundance of Hole 16-158. 334 records from Caracterización florística de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 2382 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del piedemonte de Arauca, municipio de Tame. 1766 records from SPF-Algae - Herbário da Universidade de São Paulo - Coleção de Algas. 3 records from Nannofossil abundance of Hole 3-22. 2 records from Nannofossil abundance of Hole 16-155. 10 records from Nannofossil abundance of Hole 16-157. 2 records from Nannofossil abundance of Hole 16-157A. 31 records from Nannofossil abundance of Hole 4-23. 128 records from Nannofossil abundance of Hole 4-25. 13 records from Nannofossil abundance of Hole 4-25A. 114 records from Nannofossil abundance of Hole 4-29. 21 records from Nannofossil abundance of Hole 4-29B. 101 records from Nannofossil abundance of Hole 4-30. 87 records from Nannofossil abundance of Hole 4-31. 1316 records from Recurso hidrobiológico de los manglares de la Zona de Uso Sostenible de la Balsa (ZUSLB) y la Zona de Recuperación de Tinajones (ZRT). 22 records from Nannofossil abundance of Hole 39-355. 126 records from Nannofossil abundance of Hole 39-357. 17 records from Clarification of the katydid genus Uchuca Giglio-tos, 1898 (Orthoptera: Tettigoniidae): A new species in the Brazilian Amazon Rainforest. 14 records from Heteroptera. 40 records from Nannofossil abundance of Hole 14-142. 2 records from Nannofossil abundance of Hole 14-144A. 1572 records from SBMNH Vertebrate Zoology. 4 records from A new species of the loricariid catfish genus Hemipsilichthys from southern Rio de Janeiro coastal rivers, southeastern Brazil (Teleostei: Siluriformes).. 3018 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá. 6 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 25 records from Ostracoda abundance of Hole 34-320. 27 records from Ostracoda abundance of Hole 34-320B. 12 records from Description of a new Batrochoglanis species (Siluriformes, Pseudopimelodidae) from the rio Paraguai basin, State of Mato Grosso, Brazil.. 112 records from Colección Ictiológica del Instituto Alexander von Humboldt. 7 records from Taxonomy and phylogenetic relationships among species of the seasonal, internally inseminating, South American killifish genus Campellolebias (Teleostei: Cyprinodontiformes: Rivulidae), with the description of a new species.. 6 records from Phytoplankton abundance at station Rigel_3_2005-07 in July 2005, Chipana, Chile. 5 records from Phytoplankton abundance at station Rigel_5_2005-07 in July 2005, Chipana, Chile. 5 records from Phytoplankton abundance at station Casma_2003-06-04_1, Casma, Peru. 574 records from Colección de Entomología - Curculionidae. 467 records from (Appendix B) Benthic foraminifera extinction group polpulation of ODP Site 202-1237. 4 records from A new species of Hyphessobrycon Durbin (Characiformes: Characidae) from rio Aripuanã, rio Madeira basin, Brazil. 2261 records from EFC - Herbário Escola de Florestas Curitiba. 35593 records from ASE - Herbário da Universidade Federal de Sergipe. 575 records from ZUEC-HYM - Coleção de Hymenoptera do Museu de Zoologia da UNICAMP. 6291 records from CM Herps Collection. 81 records from Colección de Referencia de Poliquetos del Museo de Ciencias de la Universidad El Bosque. 50416 records from UEC - Herbário da Universidade Estadual de Campinas. 123 records from (Table 2) Ostracode assemblages and environment characteristica of modern surface sediment samples from Patagonia, Argentina. 1892 records from Physical properties and geochemical composition of sediment cores PTA02-04, PTA03-12 and PTA03-13 from Laguna Potrok Aike, Patagonia. 48 records from (Appendix C) Average nannofossil abundances in mid-Pliocene sediments from the equatorial Atlantic. 695 records from Relative abundance of Neogene nannofossils at ODP Site 138-846 from the eastern equatorial Pacific. 1 records from Two new species of Pamphobeteus Pocock 1901 (Araneae: Mygalomorphae: Theraphosidae) from Brazil, with a new type of stridulatory organ. 475 records from UWBM Herpetology Collection (Arctos). 44 records from Inventario de Anfibios y Reptiles Mámbita. 1378 records from A geographic distribution database of Mononychellus mites (Acari: Tetranychidae) on cassava (Manihot esculenta). 121 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541. 144 records from Coiling ratios of Pulleniatina spp. in sediments from DSDP Hole 15-154A. 262 records from Coiling ratios of Pulleniatina spp. in sediments from DSDP Hole 16-157. 2085 records from Hormigas de la transición matriz - borde - interior de bosque de Fragmentos de Bosque Seco Tropical del Valle del Cauca. 8665 records from FUEL - Herbário da Universidade Estadual de Londrina. 105 records from Ohio State University Tetrapod Division - Mammal Collection (OSUM). 67 records from MSB Parasite Collection (Arctos). 6 records from Zariquiey Collection. Biological Reference Collections ICM CSIC.. 12554 records from Field Museum of Natural History (Zoology) Insect, Arachnid and Myriapod Collection. 258 records from Northern Territory Museum and Art Gallery provider for OZCAM. 959 records from Lichen herbarium, Oslo (O). 15 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 108969 records from ICN - Universidad Nacional de Colombia. 1030 records from Planktic foraminifera counts of sediment core V15-168. 486 records from Planktic foraminifera counts of sediment core V22-26. 933 records from Planktic foraminifera counts of sediment core V25-56. 2403 records from Registros biológicos de especies de fauna vertebrada terrestre en la central hidroeléctrica Miel I - 2007. 58 records from Planktic foraminifera counts of sediment core V28-122. 6992 records from ZUEC-LEP - Coleção de Lepidoptera do Museu de Zoologia da UNICAMP. 56296 records from LACM Vertebrate Collection. 13 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 31 records from Herbario XAL del Instituto de Ecología, A.C., México (IE-XAL). 11 records from Natural History Museum Rotterdam (NL) - Chordata collection. 1 records from Colección de Oligoquetos Acuáticos de la UPV/EHU. 2 records from Colección de Monocotiledóneas Mexicanas (UAM-I). 137 records from Colección Nacional de Equinodermos Mexicanos (ICMyL-DF, UNAM). 2610 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Támesis, Antioquia. 48 records from Estación Experimental de Zonas Áridas (CSIC): EEZA-Herpet. 2 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 2 records from Collection Crustacea ZMG. 1 records from Insecta ZMK. 8 records from Jardin botanique de Montréal (JBM). 18 records from ZUEC-CNI - Coleção de Cnidaria do Museu de Zoologia da UNICAMP. 68 records from ZUEC-POR - Coleção de Porifera do Museu de Zoologia da UNICAMP. 2 records from New taxa and some clarification of the tribe Steirodontini (Orthoptera: Tettigoniidae; Phaneropterinae): Tenth contribution to the suprageneric organization of Neotropical phaneropterines. 5690 records from HJ - Herbario Jataiense Prof. Germano Guarim Neto. 104 records from ZUEC-ASC - Coleção de Ascidiacea do Museu de Zoologia da UNICAMP. 1 records from Akita Prefectural Museum:Hiroki Watanabe Collection of mollusca. 3358 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 1 records from Insect Collection of Yokosuka City Museum. 1187 records from EAFM - Herbário do Instituto Federal de Educação, Ciência e Tecnologia do Amazonas. 3883 records from SOMBASE BIOCONSTRUCTORS. 125 records from IZIKO South Africa Museum Collection (1800-2013). 54 records from Amphipoda Hyperiidea of the Southern Ocean: catalogue and occurrences. 416 records from Biogeographic distribution of the Antarctic and Sub-Antarctic brachiopods (living forms). 127 records from Biogeographic distribution of Antarctic and sub-Antarctic Cumacea. 3 records from Antarctic and sub-Antarctic Lophogastrida occurrences. 88 records from Biogeographic distribution of Antarctic and sub-Antarctic Mysida. 4 records from A new genus of katydid from the Amazon Rainforest (Orthoptera: Tettigoniidae; Phaneropterinae; Steirodontini): Ninth contribution to the suprageneric organization of the Neotropical phaneropterines. 53 records from Museo Argentino de Ciencias Naturales (MACN), Buenos Aires: sea stars collection (Asteroidea, Echinodermata). 12 records from Mitochondrial lineages in the Antarctic sea slug Doris kerguelenensis. 5 records from Antarctic Marine Species Sequence Data. 1 records from South American Antarctic Marine Biodiversity Literature. 290 records from SO-Polylist. 73 records from SOVIET ANTARCTIC EXPEDITIONS for Zooplankton (R.V. OB March-May 1956, January-March 1957;R.V.ACADEMIC KURCHATOV, October 1971-January 1972; RV DMITRY MENDELEEV;R.V.ACADEMIC IOFFE 1992).. 3165 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Santuario de Flora y Fauna Los Colorados. 1 records from Collection Bryozoa - ZIM Hamburg. 1 records from Collection Cnidaria - ZIM Hamburg. 218 records from Collection Crustacea - ZIM Hamburg. 16 records from Collection Oligochaeta - ZIM Hamburg. 37 records from Collection Polychaeta - ZIM Hamburg. 3 records from Collection Bryozoa - ZMB. 10 records from Collection Cnidaria - ZMB. 536 records from Collection Crustacea - ZMB. 66 records from Collection Echinodermata - ZMB. 12 records from Collection Hydrozoa - ZMB. 93 records from Collection Porifera - ZMB. 73 records from Collection Vermes - ZMB. 1 records from Collection Ornithologie - ZSRO. 4 records from Collection Polychaeta - ZSRO. 18 records from Tiroler Landesmuseum Ferdinandeum. 165 records from The Fungal Collection at the Botanische Staatssammlung München. 25 records from Ant'Phipoda Database (New records). 1 records from Antarctic Amphipoda. 3 records from Antarctic Nemertea. 6552 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 1242 records from The Lichen Collection at the Botanische Staatssammlung München. 6 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 1986 records from The Fungal and Lichen Collections at the Herbarium Marburgense. 4970 records from Universidad Autónoma de Madrid, Biología, Acalypha. 2 records from Natural History Museum Rotterdam (NL) - Invertebrata miscellaneous Collection. 1560320 records from Tropicos Specimen Data. 33258 records from Coleção de Entomologia do Laboratório de Biologia Vegetal. 108 records from Benthic foraminifera abundance in ODP Leg 155 holes. 2659 records from British Antarctic Survey Argos satellite tracking data. 442 records from SOMBASE PYCNOGONIDS. 780 records from (Table S1) Relative abundances of coccolithophore taxa in surface sediment samples from the Equatorial and Southeastern Pacific. 2698 records from Natural History Museum Rotterdam (NL) - Mollusca collection. 11 records from (Table 6) Chemical composition of basalts from the Mid-Atlantic Ridge in the Doldrums Fault Zone. 403 records from Western Australian Museum provider for OZCAM. 10 records from Computarización de la Colección Nacional de Peces del Instituto de Biología UNAM. 24 records from (Table 4) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-681A. 102 records from (Table 3) Distribution of silicoflagellates, actiniscidians, and ebridians in selected samples from ODP Hole 112-685A. 135 records from (Table 2) Distribution of silicoflagellates, actiniscidians, and ebridians in selected samples from ODP Hole 112-683A. 9 records from (Table 3) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-680A. 30 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 230 records from (Table 2) Range chart for planktonic foraminifers from ODP Hole 111-677B. 50 records from (Table 5) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-682A, Part I. 18 records from (Table 6) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-683A, Part I. 27 records from (Table 12) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-688A. 20 records from (Table 6) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-683B. 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 149 records from A multi-proxy investigation of sediment core GeoB7165-1 ~60 km offshore Concepción. 1763 records from (Table 9) Distribution of planktonic foraminifers in ODP Site 112-687. 4272 records from (Table 7) Distribution of planktonic foraminifers in ODP Hole 112-685A. 1584 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 112-681. 2014 records from (Table 10) Distribution of planktonic foraminifers in ODP Hole 112-688A. 268 records from (Table 5) Relative abundance of benthic foraminifera in ODP Hole 112-686A. 26 records from Aschelminthes - SMF. 279 records from (Table 3) Relative abundance of benthic foraminifera in ODP Hole 112-681A. 110 records from Succession of benthic hard-bottom communities abundance at station Errina2012_MDD3. 230 records from (Table 1) Relative abundance of benthic foraminifera in ODP Hole 112-679D. 293 records from (Table 6) Relative abundance of benthic foraminifera in ODP Hole 112-687A. 93 records from (Table 7) Relative abundance of benthic foraminifera in ODP Hole 112-683B. 172 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part I. 31 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part III. 155 records from (Table 9) Relative abundance of benthic foraminifera in ODP Hole 112-685A. 184 records from (Table 10) Occurrence of benthic foraminifera in ODP Hole 112-688A. 81 records from (Table 10) Occurrence of benthic foraminifera in ODP Hole 112-688E, Part I. 120 records from (Table 10) Occurrence of benthic foraminifera in ODP Hole 112-688E, Part II. 5298 records from Caracterización del hábitat de poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en Paz de Ariporo, Casanare. 1 records from On a new marine podocopid genus and species (Ostracoda: Hemicytheridae) from Brazil. 21 records from Integrative taxonomic re-description of Halisarca magellanica and description of a new species of Halisarca (Porifera, Demospongiae) from Chilean Patagonia. 36 records from Taxonomic revision of the Neotropical Myrmicinae ant genus Blepharidatta Wheeler. 68 records from paleovertebrados. 1584 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 72 records from (Table 1) Distribution of silicoflagellates, actiniscidians, and ebridians in selected samples from ODP Hole 112-682A. 44 records from Distribution of late Neogene age calcareous nannofossils in ODP Hole 111-677A (Table 2). 398 records from SysTax - Zoological Collections. 1293 records from Pliocene-Pleistocene distribution of benthic foraminifers from ODP Hole 110-672A (Table 2). 31 records from (Table 5) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-682A, Part II. 58 records from (Table 7) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-684A. 32 records from (Table 8) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-685A. 24 records from (Table 6) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-683A, Part II. 1005 records from (Table 6) Distribution of live benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 2. 1191 records from (Table 7) Distribution of dead benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 2. 18 records from (Table 10) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-686. 17 records from (Table 11) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-687A. 140 records from (Table 7) Distribution of dead benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 1. 66 records from (Table 12) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-688E, Part II. 19 records from (Table 12) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-688E, Part I. 3950 records from (Table 3) Distribution of planktonic foraminifers in ODP Hole 112-682A. 6020 records from (Table 4) Distribution of planktonic foraminifers in ODP Hole 112-683A. 400 records from (Table 5) Distribution of planktonic foraminifers in ODP Hole 112-683B. 1134 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 1815 records from (Table 8) Distribution of planktonic foraminifers in ODP Site 112-686. 945 records from (Table 11) Distribution of planktonic foraminifers in ODP Hole 112-688E. 282 records from (Table 7) Relative abundance of benthic foraminifera in ODP Site 112-683. 12 records from A new fungus-growing ant genus, Mycetagroicus gen. nov. with the description of three new species and comments on the monophyly of the Attini (Hymenoptera: Formicidae).. 197 records from (Table 7) Relative abundance of benthic foraminifera in ODP Hole 112-683A. 271 records from (Table 4) Relative abundance of benthic foraminifera in ODP Hole 112-684A. 141 records from (Table 2) Relative abundance of benthic foraminifera in ODP Hole 112-680B. 81 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part IV. 309 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part II. 836 records from (Appendix 1) Late Cretaceous benthic foraminifera of ODP Hole 207-1257A. 950 records from (Appendix 2) Late Cretaceous benthic foraminifera of ODP Site 207-1259. 66 records from Naturhistorisches Museum Mainz, Botanical Collection. 22 records from Naturhistorisches Museum Mainz, Zoological Collection. 730 records from SOUTHERN OCEAN ISOPODA. 1 records from Southern Ocean octopus. 6 records from Botanical Research Intitute of Texas. 3359 records from (Appendix) Relative abundance of planktonic foraminifera in ODP Site 138-846 late Quaternary sediments. 74313 records from Natural History Museum (London) Collection Specimens. 23 records from Planktonic foraminifera in ODP Hole 112-688A (Table 1). 7 records from ZUEC-BRA - Coleção de Brachiopoda do Museu de Zoologia da UNICAMP. 150 records from (Table 7) Dinoflagellate cyst species distribution in ODP Hole 112-680B. 175 records from (Table 6) Dinoflagellate cyst species distribution in ODP Hole 112-679D. 35 records from (Table 4) Foraminiferal species in DSDP Sample 78-541-8-3,141-143 and Section 78-541-8-CC. 81 records from A taxonomic revision of the ground spiders of the genus Apopyllus (Araneae: Gnaphosidae). 363 records from Registros de plantas obtenidos en el monitoreo de una de las plataformas instaladas por CORNARE en Antioquia. 36 records from (Table 2) Dissolution index (XDX) values and average test mass for four species of planktonic foraminifera. 60 records from (Table 5) Quality control of palynoclasts, palynomorphs and microplankton abundances in ODPHole 112-686B. 115 records from (Table 2) Abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 4 records from (Appendix B) Abundances of components in ODP Hole 112-680B, core 2H. 871 records from (Appendix D) Analyses of the benthic foraminifer assemblage at ODP Hole 112-680B. 214 records from (Appendix C) Analyses of the benthic foraminifer assemblage at ODP Hole 112-679D. 79 records from (Appendix E) Analyses of the benthic foraminifer assemblage at ODP Hole 112-681B. 154 records from (Table 8) Dinoflagellate cyst species distribution in ODP Hole 112-681B. 132 records from (Table 9) Dinoflagellate cyst species distribution in ODP Hole 112-684B. 154 records from (Table 10) Dinoflagellate cyst species distribution in ODP Hole 112-686B. 119 records from (Table 11) Dinoflagellate cyst species distribution in ODP Hole 112-687B. 40 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 1 records from Myriapoda - SMF. 37 records from Palynological analysis of sediment core GeoB3910-2. 1393 records from Lepidoptera from Rancho Grande, Rondônia, Brasil. 2050 records from (Table 1) Distribution of nannofossil species in ODP Hole 110-671B. 27 records from Occurrence data of Plyomydas (Diptera: Asiloidea: Mydidae). 111 records from Botanical Museum, Copenhagen, the Phycology Herbarium. 5193 records from Natural History Museum, Vienna - Herbarium W. 29 records from Leaf-mining Nepticulidae (Lepidoptera) from record high altitudes: documenting an entire new fauna in the Andean páramo and puna. 17 records from Sistemática del género Polianthes L (Agavaceae). 51320 records from Macaulay Library Audio and Video Collection. 1 records from Catálogo de autoridad taxonómica del género Quercus, Fagaceae en México. 26 records from Actualización sistemática y electrónica del acervo de gasterópodos de la Colección Malacológica Dr. Antonio García-Cubas (COMA), del Instituto de Ciencias del Mar y Limnología, UNAM. 1 records from Sistemática y biogeografía del género Reithrodontomys (Rodentia: Muridae). 146 records from Cnidarios, poliquetos, crustáceos (decápodos) y quetognatos pelágicos del Golfo de California. 1 records from Computarización de la Colección Nacional de insectos Dr. Alfredo Barrera Marín del Museo de Historia Natural de la Ciudad de México. 1 records from Estudio sistemático y ecológico del género Tigridia (Iridaceae). 2294 records from Computarización del Herbario ENCB, IPN. Fase IV. Base de datos de la familia Pinaceae y de distintas familias de la clase Magnoliopsida depositadas en el Herbario de la Escuela Nacional de Ciencias Biológicas, IPN. 4 records from Computarización de la Colección de Microorganismos de importancia acuícola del CIAD, AC. 9 records from UAM Insect Collection (Arctos). 177 records from Colección de Quelonios Museo de La Salle Bogotá (MLS). 152 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 31 records from Helmintos parásitos de peces del sureste de México. 1 records from Recuento de la diversidad florística de Veracruz. 293 records from Registros biológicos de especies de fauna vertebrada terrestre en la central hidroeléctrica Miel I - 2009. 1 records from Actualización de la base de datos del Atlas Mastozoológico de México. 3 records from Mollusk Collection of Yokosuka City Museum. 766 records from Harold W. Manter Laboratory of Parasitology Collection. 3 records from Tartu University, palaeontology collections. 8 records from Ohio State University Fish Division (OSUM). 12 records from Naturkundemuseum im Ottoneum Kassel, Entomological Collection. 54 records from Nekton and plankton counts from Wechselnetz-Hai (300 µm) hauls of cruise GAE 1975/76. 5 records from (Table 2) Biomass of cysts and active infusoria in waters of the Peru coast area. 2659 records from Herpetology Collection - Instituto Nacional de Pesquisas da Amazônia. 183 records from Distribution of living benthic foraminifera in sediment cores of cruise M77 Leg 1 and 2, 63-2000 µm fraction. 1 records from ISU Mammals. 4162 records from Field Museum of Natural History (Botany) Fungi Collection. 67 records from Nekton and plankton counts from RMT (320 µm) hauls of cruise GAE 1975/76. 129 records from Nekton and plankton counts from neuston net (300 µm) hauls of cruise GAE 1975/76. 271682 records from NMNH Extant Specimen and Observation Records. 4407 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 6 records from The Fungal Collection of Helga Große-Brauckmann at the Botanische Staatssammlung München. 119 records from Herbarium Senckenbergianum (FR) - Fungi. 7 records from Collection Copepoda - SMF. 10 records from Collection Onychophora - SMF. 151 records from Levantamento da vegetação arbustiva do Parque Nacional do Jaú. 48 records from Collection Ornithologie - SNSD. 214 records from Collection Malakologie - SNSD. 1358 records from Collection Ichthyologie - SNSD. 1 records from Collection Crustacea - SNSD. 1325 records from Edaphobase. 17520 records from Partial Amphibians Collection. 1795 records from Swiss Psyllid (Hemiptera) Collections - Geneva. 836 records from Mountain Invasion Research Network (MIREN) survey. 453 records from Swiss Psyllid (Hemiptera) Collections - Basel. 78 records from Invertebrate collection. 3120 records from Parasitic Platyhelminthes Collections. 8737 records from Andes to Amazon Biodiversity Program. 2348 records from SOMBASE. 5066 records from ANTARCTIC PLANT DATABASE. 1 records from Nearctic Spider Database. 291 records from Fungal Biodiversity Centre (CBS) - Fungi strains. 172 records from Seabirds of the Southern and South Indian Ocean. 108 records from Australian Antarctic Division Herbarium. 28532 records from ARGOS Satellite Tracking of animals. 5 records from National Whale and Dolphin Sightings and Strandings Database. 112 records from Southern Ocean Continuous Zooplankton Recorder (SO-CPR) Survey. 12 records from Canadian Museum of Nature Bird Collection. 55 records from Canadian Museum of Nature Amphibian and Reptile Collection - Anura. 44 records from Canadian Museum of Nature Fish Collection. 7 records from Canadian Museum of Nature Mollusc Collection - Unionoida. 271 records from Canadian Museum of Nature Herbarium. 686 records from UWBM Mammalogy Collection. 2063 records from UWBM Ornithology Collection. 344 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 56 records from UWFC Ichthyology Collection. 1104 records from UF Florida Museum of Natural History Mammals. 195 records from University of Florida Herpetology. 4436 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 89516 records from The AAU Herbarium Database. 134 records from Revision of the South American genus Tetragonopterus Cuvier, 1816 (Teleostei: Characidae) with description of four new species. 1 records from Real Jardin Botanico, Madrid: MA-Algae. 1343 records from Real Jardin Botanico, Madrid: MA-Musci. 31 records from Real Jardin Botanico, Madrid: MA-Hepat. 4 records from Real Jardin Botanico, Madrid: MA-Lichen. 91 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 73 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 16261 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 43 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 5 records from CIBIO, Alicante:ABH-GBIF. 722 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 257 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF-Lich. 199 records from NYSM Mammals. 1 records from Acromyrmex charruanus: a new inquiline social parasite species of leaf-cutting ants. 424 records from Herbario de la Universidad de Sevilla. 49 records from Institut Botanic de Barcelona, BC. 5297 records from EPA'S EMAP Database. 48552 records from HMAP-History pf Marine Animal Populations (CoML). 5580 records from NODC WOD01 Plankton Database. 1154 records from SeamountsOnline (seamount biota) (CoML). 737 records from Colección Mastozoológica de la Universidad Industrial de Santander. 5410 records from Natural Geography In Shore Areas (NaGISA) Dataset. 16 records from Bishop Museum Data (OBIS distribution) (USOBIS). 130 records from Generic Taxonomic Database System on Mysida and Nematoda. 296 records from Academy of Natural Sciences OBIS Mollusc Database. 4882 records from SEAMAP - marine mammals, birds and turtles. 1713 records from Hexacoral Database. 48 records from Atlantic Reference Centre (OBIS Canada). 1 records from Electronic Atlas of Ichthyoplankton on the Scotian Shelf of North America (OBIS Canada). 32 records from Canadian Museum of Nature - Fish Collection (OBIS Canada). 439 records from ChEssBase (CoML). 1 records from Taxonomic Information Sytem for the Belgian coastal area (EurOBIS). 3899 records from Locations of seals in Patagonian Large Marine Ecosystem (OBIS South America, AR-OBIS, Sub-node). 2069 records from Demersal and pelagic species of fish and squid from the Patagonian shelf. 2810 records from REVIZEE Score Sul / Bentos (OBIS South America, BRAZIL). 4500 records from Paranaguá Bay - Plankton and Benthos Database (OBIS South America, BRAZIL). 1888 records from REVIZEE South Score / Pelagic and Demersal Fish Database (OBIS South America, BRAZIL). 22042 records from SINBIOTA - marine data (OBIS South America, BRAZIL). 4129 records from REVIZEE South Score / Pelagic and Demersal Fish Database II (OBIS South America, BRAZIL). 5395 records from Fishes in the Argentine Sea from 1967 to the present time. 154 records from iziko South African Museum - Fish Collection (AfrOBIS). 5 records from iziko South African Museum - Marine Mammal Collection (AfrOBIS). 551 records from FPN-EH-AVES - Breeding Distribution of seabirds in Patagonia Argentina coast. 602 records from iziko South African Museum - Shark Collection (AfrOBIS). 7 records from iziko South African Museum - Mollusc Collection (AfrOBIS). 586 records from Distribution ashore and breeding places of southern elephant seals. 1755 records from Cetacean distribution in the South Atlantic and South Pacific Ocean (AR-OBIS). 6399 records from Benthic biodiversity along the central coast in the Brazilian EEZ (OBIS South America, BRAZIL) (OBIS South America, BRAZIL). 115616 records from MICROBIS database. 559 records from Polycystine Radiolarians from the water column and the surface sediments of the World Ocean. 1237 records from Distribution of nematodes in Patagonia Argentina coast (OBIS South America, SOUTHERN OCEAN SUB-NODE). 144 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 3920 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo Páramos Chilí - Barragán, Tolima. 5 records from LSUMZ Herps Collection. 7587 records from Michigan State University Herbarium Lichens. 689 records from BYU Herpetology Collection. 8166 records from LSUMZ Mammals Collection. 37768 records from Paleobiology Database. 27191 records from herbario. 75 records from University of Amsterdam (NL) - Páramo Vegetation Research, Paramos "Guantiva -La Rusia", Colombia. 5 records from The Neotropical cuckoo wasp genus Ipsiura Linsenmaier, 1959 (Hymenoptera: Chrysididae): revision of the species occurring in Brazil. 51 records from Fish collection of National Museum of Nature and Science. 1 records from Individual Sightings. 1 records from NBM Unionoids. 78 records from NBM birds. 22 records from ZUEC-BRY - Coleção de Bryozoa do Museu de Zoologia da UNICAMP. 110898 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 4327 records from Mammals Specimens. 1 records from Birds Specimens. 189 records from SDNHM Birds Collection. 428 records from SDNHM Herpetology Collection. 383 records from Arizona State University Amphibian and Reptile Collection. 4396 records from Arizona State University Lichen Collection. 95 records from Galathea II, Danish Deep Sea Expedition 1950-52. 5 records from Botanical Museum, Copenhagen. Database of type specimens. 83 records from P. W. Lund collection in the National History Museum of Denmark, Copenhagen. 6 records from The University of Hong Kong Herbarium. 5582 records from DAV UC Davis Center for Plant Diversity. 1 records from FHSM Mammals Collection. 2393 records from Lepidoptera collection of Hannu Saarenmaa. 163 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 41 records from (Table 5) Foraminiferal species and fluctuations of the dissolution index of two samples, representing the dissolution pattern during the late Pliocene at DSDP Hole 78-541. 226 records from Herbarium (UNA). 460 records from CNMA/Colección Nacional de mamíferos. 1096 records from MEXU/Plantas Vasculares. 108 records from MEXU/Tipos de plantas vasculares. 10 records from CNPE/Coleccion Nacional de Peces. 1709 records from MEXU/Colección de Briofitas. 7 records from Taxonomic revision of Stagmatoptera Burmeister, 1838 (Mantodea: Mantidae, Stagmatopterinae). 6 records from CNCR/Colección Nacional de Crustaceos. 135 records from Actualización de las bases de datos del Herbario XAL. Fase III. 2 records from CNIN/Tipos Odonata. 3324 records from Mariposas (Lepidoptera: Papilionoidea) de la Colección Entomológica del Instituto Alexander von Humboldt. 1 records from Schulman's Neotropical Adelobotrys database. 1056 records from Mammal specimens. 4 records from MMNH Museum Bird Collection. 846 records from Invertebrate Paleontology Division, Yale Peabody Museum. 21608 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 1089 records from Invertebrate Zoology Division, Yale Peabody Museum. 431 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 13557 records from TTU Mammals Collection. 36 records from Algaterra Types. 1131 records from (Appendix A1) Abundances of planktonic and benthic foraminifera in the Turonian to Coniacian sediments of ODP Site 207-1259. 978 records from Herbarium Berolinense. 19637 records from Lichen Herbarium Berlin. 4 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 1724 records from Centre for Genetic Resources, the Netherlands, PGR passport data. 7113 records from Biologiezentrum Linz. 6890 records from United States National Plant Germplasm System Collection. 189 records from Administración Nacional de Institutos y Laboratorios de Salud. 47934 records from The System-wide Information Network for Genetic Resources (SINGER). 147 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 24 records from The Erysiphales Collection at the Botanische Staatssammlung München. 194 records from The Erysiphales Collection at the University Halle-Wittenberg. 595 records from The Myxomycetes Collections at the Botanische Staatssammlung München - Collection of Hermann Neubert. 691 records from The Myxomycetes Collections at the Botanische Staatssammlung München - Collection of Martin Schnittler. 8 records from The Myxomycetes Collections at the Botanische Staatssammlung München - Main Collection. 212 records from Nordic Genetic Resources. 249 records from USU-UTC Specimen Database. 9391 records from Planetary Biodiversity Inventory Eumycetozoan Databank. 11210 records from UF Invertebrate Zoology. 2606 records from The Collection of Fungi of the Real Jardín Botánico of Madrid (MA-Fungi). 9 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-HEPATICAE. 5 records from Institut Botanic de Barcelona, BC-Histórico. 2 records from Fish Collection of Natural History Museum and Institute, Chiba. 13 records from HBGSpermatophyta - Herbarium Hamburgense. 189 records from Fish larvae biodiversity along the central coast in the Brazilian EEZ (OBIS South America, BRAZIL) (OBIS South America, BRAZIL). 135 records from Zooplankton biodiversity along the central coast in the Brazilian EEZ (OBIS South America, BRAZIL) (OBIS South America, BRAZIL). 263 records from The Myxomycetes Collection at the V. L. Komarov Botanical Institute, St. Petersburg. 945 records from Estacion Biologica Donana - CSIC, Mammal Collection. 74 records from Inventory of Antarctic seabird breeding sites. 888 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 652 records from Harvard University Herbaria. 1 records from UCLA Donald R. Dickey Bird and Mammal Collection. 4 records from DSMZ Prokarya Collection Catalogue. 294 records from Hawk Migration Association of North America - HawkCount. 487 records from Galapagos grasses and sedges. 1595 records from EURISCO, The European Genetic Resources Search Catalogue. 17503 records from Atlantic and Gulf Rapid Reef Assessment -Benthic (OBIS Australia). 2364 records from CVRD - Herbário da Reserva Natural Vale. 5 records from Colección de Referencia de Platelmintos del Museo de Ciencias de la Universidad El Bosque. 64 records from Characidium longum (Characiformes: Crenuchidae), a new fish from Venezuela.. 38322 records from Coleção Entomológica Paulo Nogueira-Neto - IB/USP. 14416 records from Coleção Entomológica Pe. Jesus Santiago Moure (Hymenoptera). 6426 records from MAR - Herbário do Maranhão. 18136 records from Coleção Entomológica Moure e Costa. 9614 records from Coleção Entomológica do Depto. de Sistemática e Ecologia. 3056 records from Laboratório de Ecologia e Biogeografia de Insetos da Caatinga. 5860 records from Coleção de Abelhas do Museu de Ciências e Tecnologia da PUCRS. 20637 records from MAL. 1916 records from Distribution of planktic foraminifera in surface sediments of the Atlantic Ocean. 3580 records from Planktic foraminifera counts in surface sediment samples. 192 records from Planktic foraminiferal assemblage for the 10kyr time slice from different sediment cores. 1 records from The genus Zelurus Hahn, 1826, in Brazilian caves: description of new species and comments on the potential distribution of the genus in South America. 339 records from Distribution of planktonic foraminifera in surface sediment samples A180-072 to V23-83. 1496 records from Modern planktic foraminifera assemblage from surface sediment samples used as reference data set for the reconstruction of Atlantic sea surface temperatures during the last glacial maximum (LGM). 3477 records from Aves laguna El Tinije. 834 records from Distribution of planktic foraminifera at the last glacial maximum. 1895 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 8143 records from Distribution of planktic foraminifera of sediment core M35003-4. 5641 records from Distribution of planktic foraminifera of sediment core M35027-1. 863 records from Distribution of planktic foraminifera in surface sediments. 906 records from Percentages of planktonic foraminifera species in sediment core V15-168. 4008 records from Composition of planktonic foraminifera species in 1123 surface sediment samples compared with sea surface temperatures from the Levitus Atlas. 3447 records from Distribution of planktic foraminifers of core 138-846B. 4485 records from Distribution of planktic foraminifers of core RC13-110. 2098 records from Distribution of planktic foraminifers of core V19-29. 264 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (rescate). 1368 records from Distribution of planktic foraminifers of core Y71-06-12. 1377 records from Composition of planktonic foraminifera species from 310 sediments samples during the last glacial maximum. 831 records from Time slice 2 of planktic foraminifera of the last glacial maximum. 2176 records from Distribution of planktic foraminifera in surface sediments of the Atlantic Ocean (ATL947). 1 records from UAM Herbarium (ALA), Algae Collection (Arctos). 177494 records from Primer censo de plantas leñosas de una Parcela Permanente de 25 hectáreas, ubicada en la Reserva Natural La Planada (Nariño, Colombia). 12 records from Typhlomyrmex meire, a remarkable new species endemic to Southern Bahia, Brazil (Formicidae: Ectatomminae).. 1156 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia.. 11729 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en el Complejo de Páramos Chingaza. 2774 records from Relative abundance of planktic foraminifera in sediment core GeoB1523-1. 3569 records from Relative abundance of planktic foraminifera in sediment core GeoB2204-2. 156 records from Abundance of planktonic foraminifera in surface sediments of the South Atlantic. 600 records from Bulk components, concentration and planktonic foraminifera of sediment core GeoB7112-5. 1158 records from Bulk components and planktonic foraminifera of sediment core GeoB7139-2. 804 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 424 records from Bulk components and planktonic foraminifera of sediment core GeoB3375-1. 806 records from Bulk components and planktonic foraminifera of sediment core GIK17748-2. 890 records from Percentages of planktonic foraminifera species in sediment core RC09-49. 649 records from Percentages of planktonic foraminifera species in sediment core RC13-184. 870 records from Percentages of planktonic foraminifera species in sediment core V22-38. 3 records from A new species of Rhagovelia Mayr, 1865 (Hemiptera: Heteroptera: Veliidae) from Pará State, with an updated key to Brazilian species of the robusta group. 1339 records from Percentages of planktonic foraminifera species in sediment core V25-75. 1520 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V22-38. 5 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 359 records from Relative abundances of planktonic foraminifera from surface sediments of the Drake Passage, Southern Ocean (Table 1). 77 records from Biodiversitätsdatenbank des Landes Salzburg. 933 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (siembra). 21 records from WNMU Mammal Collection (Arctos). 1 records from Taxonomy of some little-understood North American ants (Hymenoptera: Formicidae). 6814 records from Naturalis Biodiversity Center (NL) - Aves. 62 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 2 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Algae. 242 records from (Fig. 3) Age and multiproxy studies of sediment core GeoB7186-3. 24 records from University of Alberta Museum of Zoology Amphibian and Reptile Collection (UAMZ). 44539 records from Mosquito Occurrence Dataset. 6 records from Repatriación de datos del Herbario de Arizona (ARIZ). 18405 records from Colección de artrópodos del Museo de Historia Natural de la Pontificia Universidad Javeriana. 46 records from Programa de repatriación de datos de ejemplares mexicanos. 20 records from Colección Nacional de Peces del IBUNAM. 14 records from MZFC/Coleccion de Aves. 7 records from ANTXXIII-8 Birds and Mammals. 4 records from Antarctic Krill occurrence data from Discovery expeditions. 9 records from Antarctic Euphausiacea occurence data from "German Antarctic Marine Living Resources" (GAMLR) Expeditions. 1246 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 175 records from Collections data on ecology of bottom animal of the Southern ocean. 109 records from Nemertina World Checklist. 71 records from Christopher Walker collection of Glomeromycotan fungi. 5 records from Invertebrates compiled by W.Block. 91 records from CNIN/Triatominos (Hemiptera-Heteroptera-Reduviidae). 10 records from UCM Bird Collection (Arctos). 118 records from UCM Fish Collection (Arctos). 342 records from UCM Amphibian and Reptile Collection (Arctos). 40 records from Quantitative study of evolution in the Sphaeroidinella lineage in mid-Pleistocene sediment of ODP Hole 154-926A (Appendix A). 3 records from (Table 2) Distribution of kummerform and sinistral specimens the planktic foraminifera Contusotruncana contusa in Cretaceous sediments. 78 records from CNIN/Coleoptera. 13 records from CNIN/Tipos Coleoptera. 694 records from University of Alberta E. H. Strickland Entomological Museum (UASM). 345 records from LSUMZ (LSU MNS) Fishes Collection. 20484 records from Field Museum of Natural History (Botany) Bryophyte Collection. 172 records from Colorado Plateau Museum of Arthropod Biodiversity. 1 records from Description of Cephalotes specularis n. sp. (Formicidae: Myrmicinae) - the mirror turtle ant. 88 records from (Appendix A2) Cenomanian benthic foraminifera of ODP Site 207-1260. 1398 records from Biodiversidad en las propuestas para declaratoria de Áreas Protegidas en los Municipios de Dagua, Restrepo, La Cumbre y Vijes y un Grupo de Reservas Naturales de la Sociedad Civil. 3154 records from Hormigas en cafetales con diferente intensidad de manejo en el departamento del Cauca. 19 records from Microplankton data off Chipana Bay, 2006, Chile. 19 records from Microplankton data off Mejillones, 2006, Chile. 19 records from Nanoplankton data off Chipana Bay, summer 2006, Chile. 28 records from A taxonomic review of the genus Myrmelachista (Hymenoptera: Formicidae) in Costa Rica.. 1015 records from Caracterización vegetal y rasgos funcionales de plantas colectadas en un gradiente altitudinal de bosque altoandino a páramo en el Santuario de Fauna y Flora Iguaque. 3027 records from Caracterización de fauna y flora para el establecimiento de límites funcionales de humedales en tres ventanas piloto: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo de humedales Paz de Ariporo - Hato Corozal. 848 records from WFVZ Bird Collections. 1968 records from (Appendix B) Distribution of planktonic foraminifera at DSDP Hole 72-518. 2 records from Rivulus kayapo n. sp. (Teleostei: Cyprinodontiformes: Rivulidae): a new killifish from the serra dos Caiapós, upper rio Araguaia basin, Brazil.. 3 records from Redescriptions and new host records of chewing lice of the genus Ricinus (Phthiraptera: Ricinidae) from the Neotropical Region. 11 records from Inventario de Herpetología Floreña I, Yopal, Casanare. 2230 records from Fundación Miguel Lillo - Colección Ornitológica. 4 records from Mammifères (sauf Chiroptères) du Muséum d'Histoire Naturelle de la ville de Bourges (BOUM). 160 records from USF Herbarium. 2326 records from ZUEC-MAM - Coleção de Mamíferos do Museu de Zoologia da UNICAMP. 98 records from (Figure 6k and 6l) Nannofossil accumulation rate and absolute abundances of coccoliths from ODP Site 1233. 15 records from New species and phylogenetic relationships of the spider genus Coptoprepes using morphological and sequence data (Araneae: Anyphaenidae). 590 records from Aves Bosque Seco Chicamocha. 12 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 13 records from Relative abundance of organic-walled dinoflagellate cysts in surface sediments. 1137 records from Planktic foraminifera abundance of Hole 72-516F. 1979 records from Planktic foraminifera abundance of Hole 72-518. 399 records from Planktic foraminifera abundance of Hole 14-142. 34 records from Planktic foraminifera abundance of Hole 14-144. 82 records from Planktic foraminifera abundance of Hole 14-144A. 78 records from Planktic foraminifera abundance of Hole 14-144B. 520 records from Planktic foraminifera abundance of Hole 39-357. 1 records from ZUEC-CEP - Coleção de Cephalopoda do Museu de Zoologia da UNICAMP. 54 records from Planktic foraminifera abundance of Hole 4-23. 6 records from Planktic foraminifera abundance of Hole 4-24. 428 records from Planktic foraminifera abundance of Hole 4-25. 105 records from Planktic foraminifera abundance of Hole 4-29. 68 records from Planktic foraminifera abundance of Hole 4-29B. 685 records from Planktic foraminifera abundance of Hole 4-30. 2943 records from HPAN - Herbário do Pantanal "Vali Joana Pott". 201 records from Planktic foraminifera abundance of Hole 4-31. 278 records from Planktic foraminifera abundance of Hole 39-354. 371 records from Foraminifera abundance of Hole 39-356. 1945 records from Foraminifera abundance of Hole 39-357. 54 records from Planktic foraminifera abundance of Hole 15-146. 5173 records from Planktic foraminifera abundance of Hole 15-147. 49 records from Planktic foraminifera abundance of Hole 15-147C. 1059 records from Planktic foraminifera abundance of Hole 15-148. 560 records from Planktic foraminifera abundance of Hole 15-149. 47 records from Planktic foraminifera abundance of Hole 15-150. 71 records from Planktic foraminifera abundance of Hole 15-153. 148 records from Planktic foraminifera abundance of Hole 15-154. 749 records from Planktic foraminifera abundance of Hole 15-154A. 658 records from The current status of knowledge of Coleoptera (Arthropoda, Insecta) immatures from Brazil. 1623 records from Censo de primates de la Fundación Entropika. 1018 records from Planktic foraminifera abundance of Hole 9-84. 1037 records from Evaluación del estado actual de las poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en los municipios de Paz de Ariporo y Hato Corozal, Casanare. 158 records from Planktic foraminifera abundance of Hole 16-155. 1058 records from Planktic foraminifera abundance of Hole 16-157. 776 records from Planktic foraminifera abundance of Hole 16-158. 2630 records from Planktic foraminifera abundance of Hole 68-502A. 179 records from Planktic foraminifera abundance of Hole 68-502B. 235 records from Planktic foraminifera abundance of Hole 68-502C. 12 records from Caracterización de la Íctiofauna presente en la laguna Concepción, Bocana del río Saija (Cauca), sitio sagrado de las comunidades Indígenas de OZBESCAC. 97 records from PSM Vertebrates Collection. 4 records from Planktic foraminifera abundance of Hole 54-424. 1 records from Planktic foraminifera abundance of Hole 54-424A. 3 records from Planktic foraminifera abundance of Hole 54-424B. 13 records from Planktic foraminifera abundance of Hole 54-425. 10 records from Planktic foraminifera abundance of Hole 15-154A. 47 records from Planktic foraminifera abundance of Hole 72-515. 117 records from Planktic foraminifera abundance of Hole 72-515A. 203 records from Planktic foraminifera abundance of Hole 72-515B. 811 records from Planktic foraminifera abundance of Hole 72-516. 1155 records from Planktic foraminifera abundance of Hole 72-516A. 3651 records from Planktic foraminifera abundance of Hole 72-516F. 2083 records from Planktic foraminifera abundance of Hole 72-517. 786 records from Planktic foraminifera abundance of Hole 72-518. 9 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña marzo 2007. 1582 records from KUBI Ichthyology Collection. 874 records from Natural History Museum, University of Tartu. 7 records from Oligosarcus perdido (Characiformes, Characidae), a new species of freshwater fish from Serra da Bodoquena, upper Rio Paraguai basin, Brazil.. 86 records from Computarización del Herbario ENCB. Fase II. Base de datos de los ejemplares de la familia Burseraceae y Nyctaginaceae y base de datos digitalizada de los ejemplares tipo de plantas vasculares del Herbario de la Escuela Nacional de Ciencias Biológicas. 1 records from A new genus of predatory katydids (Orthoptera: Tettigoniidae: Listroscelidinae) from the Amazonian Rainforest. 2984 records from USGS Marine Fishes of St. Croix and U.S. Virgin Islands. 93 records from Two new species of Leporinus Agassiz, 1929 (Characiformes: Anostomidae) from tributaries of the lower Amazon basin in Brazil. 876 records from Range table from planktonic foraminifers in ODP Hole 138-847B. 331 records from Range table from planktonic foraminifers in ODP Hole 141-859A. 84 records from Range table from planktonic foraminifers in ODP Hole 141-859B. 528 records from Range table from planktonic foraminifers in ODP Hole 141-860B. 58 records from Range table from planktonic foraminifers in ODP Hole 141-861A. 33 records from Range table from planktonic foraminifers in ODP Hole 141-861B. 529 records from Range table from planktonic foraminifers in ODP Hole 141-861C. 109 records from Range table from planktonic foraminifers in ODP Hole 141-861D. 54 records from Range table from planktonic foraminifers in ODP Hole 141-862A. 1 records from Range table from planktonic foraminifers in ODP Hole 141-862B. 4 records from Range table from planktonic foraminifers in ODP Hole 141-862C. 320 records from Range table from planktonic foraminifers in ODP Hole 141-863A. 172 records from Range table from planktonic foraminifers in ODP Hole 141-863B. 1061 records from University of British Columbia Herbarium (UBC) - Algae Collection. 6793 records from MLZ Bird Collection (Arctos). 808 records from Range table from planktonic foraminifers in ODP Hole 154-925B. 1142 records from Range table from planktonic foraminifers in ODP Hole 154-925A. 288 records from Range table from planktonic foraminifers in ODP Hole 154-929E. 600 records from Range table from planktonic foraminifers in ODP Hole 155-930B. 442 records from Range table from planktonic foraminifers in ODP Hole 155-930C. 37 records from Herbarium of Umeå University (UME). 260 records from Range table from planktonic foraminifers in ODP Hole 155-930D. 175 records from Range table from planktonic foraminifers in ODP Hole 155-931A. 1275 records from Range table from planktonic foraminifers in ODP Hole 155-931B. 115 records from Range table from planktonic foraminifers in ODP Hole 155-931C. 468 records from Range table from planktonic foraminifers in ODP Hole 155-932A. 156 records from Range table from planktonic foraminifers in ODP Hole 155-932B. 682 records from Range table from planktonic foraminifers in ODP Hole 155-933A. 252 records from Range table from planktonic foraminifers in ODP Hole 155-934A. 1176 records from Range table from planktonic foraminifers in ODP Hole 155-935A. 1092 records from Range table from planktonic foraminifers in ODP Hole 155-936A. 399 records from Range table from planktonic foraminifers in ODP Hole 155-937B. 672 records from Range table from planktonic foraminifers in ODP Hole 155-938A. 294 records from Range table from planktonic foraminifers in ODP Hole 155-939B. 651 records from Range table from planktonic foraminifers in ODP Hole 155-940A. 525 records from Range table from planktonic foraminifers in ODP Hole 155-941A. 273 records from Range table from planktonic foraminifers in ODP Hole 155-941B. 462 records from Range table from planktonic foraminifers in ODP Hole 155-942A. 168 records from Range table from planktonic foraminifers in ODP Hole 155-942B. 105 records from Range table from planktonic foraminifers in ODP Hole 155-942C. 441 records from Range table from planktonic foraminifers in ODP Hole 155-943A. 840 records from Range table from planktonic foraminifers in ODP Hole 155-944A. 294 records from Range table from planktonic foraminifers in ODP Hole 155-945A. 650 records from Range table from planktonic foraminifers in ODP Hole 155-946A. 243 records from Caracterización de coberturas vegetales en el páramo de Rabanal. 11 records from A new large Myloplus Gill 1896 from rio Negro basin, Brazilian Amazon (Characiformes: Serrasalmidae). 333912 records from Field Museum of Natural History (Botany) Seed Plant Collection. 3119 records from Hormigas en cultivos de naranja (Citrus sinensis (L.) Osbeck) de la costa Caribe de Colombia. 8 records from Revision of Diplosynapsis Enderlein, 1914 (Diptera, Asilidae, Asilinae) with description of four new species. 967 records from Colección Nacional de Entomología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 42173 records from MBML-Herbario - Herbário Mello Leitão. 3 records from Rediscovery of a fossil dolichoderine ant lineage (Hymenoptera: Formicidae: Dolichoderinae) and a description of a new genus from South America.. 38 records from MPM Milwaukee Public Museum Herbarium. 54 records from New records of Gerromorpha and Nepomorpha (Insecta: Hemiptera: Heteroptera) from South America. 2108 records from Ohio State University Tetrapod Division - Bird Collection (OSUM). 1 records from MCNH Museum of Cultural and Natural History Mammals Collection. 19 records from Hypostomus rhantos (Siluriformes: Loricariidae), a new species from southern Venezuela.. 46 records from Sand flies of Eastern Africa. 470 records from RBspirit - Rio de Janeiro Botanical Garden fluid-preserved specimens.. 18 records from ZUEC-EPH - Coleção de Ephemeroptera do Museu de Zoologia da UNICAMP. 146 records from Benthic foraminifera abundance of Hole 34-320. 27 records from Benthic foraminifera abundance of Hole 34-320A. 59 records from Benthic foraminifera abundance of Hole 34-320B. 197 records from Benthic foraminifera abundance of Hole 34-321. 2795 records from ZUEC-REP - Coleção de Répteis do Museu de Zoologia da UNICAMP. 38318 records from Colección Nacional de Herpetología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1349 records from Range table from benthic foraminifers in ODP Hole 141-861C. 211 records from Range table from benthic foraminifers in ODP Hole 141-861D. 10954 records from BOTU - Herbário Irina Delanova Gemtchújnicov. 3130 records from Range table from benthic foraminifers in ODP Hole 154-926A. 5514 records from Range table from benthic foraminifers in ODP Hole 154-928A. 2476 records from Range table from benthic foraminifers in ODP Hole 154-929A. 85 records from Range table from benthic foraminifers in ODP Hole 154-929B. 7742 records from MBML-Anfibios - Coleção de Anfíbios MBML. 5 records from Two new endemic species of Epictia Gray, 1845 (Serpentes: Leptotyphlopidae) from Northern Peru. 135 records from Distribution of Upper Cretaceous deep water agglutinated foraminifera in sediments of the North Atlantic and its marginal seas (Tab. 1). 67 records from Global subterranean fishes. 237 records from Homoptera. 108 records from Phytoplankton abundance off Chao island in Juli 2003, Peru. 108 records from Phytoplankton abundance off Guañape bay in Juli 2003, Peru. 180 records from Phytoplankton abundance off Guañape islands in Juli 2003, Peru. 84 records from A taxonomic revision of the neotropical termite genus Diversitermes (Isoptera: Termitidae: Nasutitermitinae). 22 records from Dinoflagellate abundance of Hole 14-144. 2 records from Dinoflagellate abundance of Hole 14-144A. 102 records from Microfossil abundance of Hole 39-354. 26 records from Microfossil abundance of Hole 39-356. 18 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 141-860B. 39 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 141-861C. 1 records from A new species of Enderleina Jewett (Plecoptera, Perlidae) from Amazonas State, Brazil. 12 records from Phytoplankton abundance in surface water in October 1995, Chimbote, Peru. 12 records from Phytoplankton abundance in surface water in October 1995, Ilo, Peru. 264 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 73 records from Phytoplankton abundance in surface water in January 1996, Chimbote, Peru. 264 records from Phytoplankton abundance in surface water in January 1996, Callao, Peru. 198 records from Phytoplankton abundance in surface water in January 1996, Pisco, Peru. 420 records from Phytoplankton abundance in surface water in January 1996, Ilo, Peru. 360 records from Phytoplankton abundance in surface water in July-August 1996, Paita, Peru. 72 records from Phytoplankton abundance in surface water in July-August 1996, Chimbote, Peru. 120 records from Phytoplankton abundance in surface water in July-August 1996, Callao, Peru. 240 records from Phytoplankton abundance in surface water in July-August 1996, Pisco, Peru. 876 records from Phytoplankton abundance in surface water in July-August 1996, Ilo, Peru. 228 records from Phytoplankton abundance in surface water in September 1996, Paita, Peru. 48 records from Phytoplankton abundance in surface water in September 1996, Chimbote, Peru. 168 records from Phytoplankton abundance in surface water in September 1996, Callao, Peru. 168 records from Phytoplankton abundance in surface water in September 1996, Pisco, Peru. 1139 records from Phytoplankton abundance in surface water in September 1996, Ilo, Peru. 108 records from Phytoplankton abundance in surface water in October 1996, Paita, Peru. 60 records from Phytoplankton abundance in surface water in October 1996, Chimbote, Peru. 168 records from Phytoplankton abundance in surface water in October 1996, Callao, Peru. 150 records from Phytoplankton abundance in surface water in October 1996, Pisco, Peru. 714 records from Phytoplankton abundance in surface water in October 1996, Ilo, Peru. 192 records from Phytoplankton abundance in surface water in March 1997, Pisco, Peru. 645 records from Phytoplankton abundance in surface water in March 1997, Ilo, Peru. 204 records from Phytoplankton abundance in surface water in June 1997, Paita, Peru. 120 records from Phytoplankton abundance in surface water in June 1997, Chimbote, Peru. 2 records from CSIRO, Australian National Algae Culture Collection, Global, 1949-2008. 384 records from Phytoplankton abundance in surface water in June 1997, Callao, Peru. 228 records from Phytoplankton abundance in surface water in June 1997, Pisco, Peru. 705 records from Phytoplankton abundance in surface water in June 1997, Ilo, Peru. 324 records from Phytoplankton abundance in surface water in September 1997, Chimbote, Peru. 216 records from Phytoplankton abundance in surface water in September 1997, Pisco, Peru. 540 records from Phytoplankton abundance in surface water in September 1997, Ilo, Peru. 528 records from Phytoplankton abundance in surface water in October 1997, Paita, Peru. 492 records from Phytoplankton abundance in surface water in October 1997, Chimbote, Peru. 400 records from Phytoplankton abundance in surface water in October 1997, Callao, Peru. 231 records from Phytoplankton abundance in surface water in October 1997, Pisco, Peru. 832 records from Phytoplankton abundance in surface water in October 1997, Ilo Peru. 444 records from Phytoplankton abundance in surface water in November 1997, Paita, Peru. 308 records from Phytoplankton abundance in surface water in November 1997, Chimbote, Peru. 72 records from Phytoplankton abundance in surface water in November 1997, Pisco, Peru. 420 records from Phytoplankton abundance in surface water in November 1997, Ilo, Peru. 195 records from Phytoplankton abundance in surface water in May 1997, Callao, Peru. 192 records from Phytoplankton abundance in surface water in August 1997, Pisco, Peru. 330 records from Phytoplankton abundance in surface water in February 1998, Pisco, Peru. 767 records from Phytoplankton abundance in surface water in February 1998, Paita, Peru. 468 records from Phytoplankton abundance in surface water in February 1998, Chimbote, Peru. 816 records from Phytoplankton abundance in surface water in February 1998, Ilo, Peru. 108 records from Phytoplankton abundance in surface water in May 1996, Chimbote, Peru. 275 records from Phytoplankton abundance in surface water in May 1996, Pisco, Peru. 444 records from Phytoplankton abundance in surface water in May 1996, Ilo, Peru. 198 records from Phytoplankton abundance at several bottle stations in may 1996, Pisco, Peru. 288 records from Phytoplankton abundance at several bottle stations in May 1996, Sechura, Peru. 785 records from Colección de Mamíferos Marinos del Centro Nacional Patagónico. 29055 records from Coleccion de sonidos ambientales. 153 records from Avistamientos de Biodiversidad Marina / Marine Biodiversity Sightings. 1510 records from Colección de Anfibios del Instituto Alexander von Humboldt. 3 records from A revision and key for the tribe Diaphorolepidini (Serpentes: Dipsadidae) and checklist for the genus Synophis. 6 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 2670 records from Colección Teriológica y Ornitológica de la Universidad Tecnológica del Chocó. 6 records from (Table 1) Dinoflagellate cyst zonations at ODP Site 202-1233. 3638 records from (Table 3) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-502A from the Caribbean Sea. 116 records from KUBI Invertebrate Zoology Collection. 7 records from R. L. McGregor Herbarium Lichen Collection. 308 records from R. L. McGregor Herbarium Vascular Plants Collection. 5 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 6 records from ABBBS Bird Banding records from the Australian Antarctic Territory and Heard Island.. 1289 records from Colección de plantas vasculares de Brasil del Herbario "Jaime Andrés Rodríguez". LEB-Brasil. 6 records from MEXU/Colección de Plantas Acuáticas. 1910 records from Senckenberg - CeDAMar Resource. 35543 records from Texas A&M University Insect Collection. 102 records from UAZ Mammals. 37 records from MGC Herbarium of University of Malaga (Spain): MGC-Cormof dataset. 13 records from Biological and palaeontological collection and observation data MNHNL. 735 records from Ifremer BIOCEAN database (Deep Sea Benthic Fauna). 1219 records from COMARGIS: Information System on Continental Margin Ecosystems. 148 records from Flora de los ecosistemas de la zona alta del río Coello (Tolima, Colombia). 217 records from Botany Division, Yale Peabody Museum. 3026 records from Entomology Division, Yale Peabody Museum. 1078 records from Vertebrate Zoology Division - Ichthyology, Yale Peabody Museum. 234 records from Paleobotany Division, Yale Peabody Museum. 1649 records from BIOLOGICAL SCIENCES DATA. 1023 records from Collection Pisces SMF. 138 records from Collection Arachnology SMF. 3 records from Collection Porifera SMF. 5313 records from HUTO - Herbário da Universidade de Tocantins. 85 records from Collection Mollusca SMF. 137 records from Collection Polychaeta SMF. 1269 records from Collection Aves (spirit preserved) SMF. 106 records from Collection Cnidaria SMF. 1839 records from Collection Herpetology SMF. 2674 records from Herbarium Senckenbergianum (FR). 33 records from Collection Aves (bird skeletons) SMF. 1688 records from Collection Aves (bird skins) SMF. 586 records from Collection Crustacea SMF. 1034 records from Collection Bryozoa SMF. 42 records from Collection Thysanoptera SMF. 34 records from Collection Tardigrada SMF. 47 records from A preliminary inventory of the catfishes of the lower Rio Nhamundá, Brazil (Ostariophysi, Siluriformes). 47 records from Collection Echinodermata SMF. 12 records from Collection Graptolithina fossil SMF. 25895 records from SINGER Coordinator. 2075 records from Fauna y flora asociada a 18 humedales del valle geográfico del río Cauca. 7 records from FSUCML Zoological Collections. 53 records from MEXU/Leguminosae. 3251 records from Ohio State Acarology Laboratory (OSAL), Ohio State University. 43 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Briof. 97 records from Database of Native Plants in Taiwan. 5114 records from AMNH Bird Collection. 8251 records from AMNH Mammal Collections. 1 records from Mycological Collection - University of Washington Herbarium (WTU). 208 records from Dinoflagellates of multicorer surface sediments. 1388 records from Caracterización de aves del borde sur de Bogotá en las localidades de Usme y Ciudad Bolívar. 89 records from Facultad de Ciencias Exactas y Naturales Universidad de Buenos Aires Coleccion BAFC de Hongos. 3 records from A new species of Campylothorax Schött, 1893 (Collembola, Paronellidae) from Brazilian Amazon, with an identification key to the genus. 624 records from Quirópteros del Parque Natural Regional El Vínculo y su zona de amortiguación (Buga, Valle del Cauca, Colombia). 18 records from Lost and found: the Plecoptera types of Blanchard and Mabille, with further contributions to the stoneflies of Chile. 4 records from University of Ghana - Ghana Herbarium. 100 records from Ophiuroidea collections of the Zoological Institute Russian Academy of Sciences. 4258 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2009. 1 records from A new species of hermit crab of the genus Pagurus Fabricius, 1775 (Crustacea: Anomura: Paguridae) from the southern Caribbean off Venezuela. 406823 records from DATAVES. 11346 records from University of Florida Invertebrate Paleontology. 48 records from New records of Gerromorpha and Nepomorpha (Insecta: Hemiptera: Heteroptera) from South America. 616 records from Entomological Collections (NHRS), Swedish Museum of Natural History (NRM). 1942 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Pereira, Risaralda. 3 records from UAM Earth Sciences Collection (Arctos). 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 17 records from Two new species of South American freshwater crayfish genus Parastacus Huxley, 1879 (Crustacea: Decapoda: Parastacidae). 29 records from The biting and predaceous midges of Guadeloupe (Diptera: Ceratopogonidae). II. Species of the subfamily Dasyheleinae. 429 records from Corales de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMco). 87234 records from Herbario Amazónico Colombiano. 2 records from Hemiodus jatuarana, a new species of Hemiodontidae from the rio Trombetas, Amazon Basin, Brazil (Teleostei, Characiformes).. 1 records from Phytotelmatrichis, a new genus of Acrotrichinae (Coleoptera: Ptiliidae) associated with the phytotelmata of Zingiberales plants in Peru. 2458 records from Colección de Tejidos del Instituto Alexander Von Humboldt. 1 records from Chilopoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 521 records from SMNS Herpetologie. 214 records from MVZ Egg and Nest Collection (Arctos). 1137 records from Plantas Acuáticas de la Orinoquía Colombiana. 1221 records from Museum of Southwestern Biology, Division of Arthropods. 4 records from Symphyla Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 16093 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Ornithology National Collection (MACNOr).. 424 records from Mamíferos voladores y no voladores del suroccidente colombiano. 16088 records from Colección Nacional de Ornitología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 3030 records from (Figure 2) Quaternary biostratigraphy and planktonic foraminifera of DSDP Hole 72-517. 4053 records from Field Museum of Natural History (Botany) Pteridophyte Collection. 55 records from UAM Herpetology Collection (Arctos). 27 records from ZUEC-GCH - Coleção de Gastrotricha do Museu de Zoologia da UNICAMP. 193 records from Inventario de Aves en la Finca Naranjitos; Aracal, Yopal, Casanare. 6 records from Description of the females of Anapis castilla and Anapisona bordeaux (Araneae, Anapidae).. 5361 records from Colección Ornitológica de la Universidad del Valle. 168 records from Registros de quirópteros de tres localidades del caribe colombiano. 13769 records from MAC - Herbário do Instituto do Meio Ambiente do Estado de Alagoas. 1137 records from (Appendix A) Distribution of planktonic foraminifera at DSDP Hole 72-516. 781 records from Inventario de Aves y Mamíferos en humedales del departamento de Córdoba. 517 records from Distribution ashore of Southern elephant seals in Península Valdés. 17 records from The subfamily Mendesellinae (Hymenoptera: Braconidae) in Brazil, with the description of six new species. 21 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 278 records from Investigación prioritaria hacia el conocimiento y conservación de tortugas amenazadas del bosque seco tropical colombiano Mesoclemmys dahli (Carrachina) y Chelonoidis carbonaria (Morrocoy). 205 records from Fortalecimiento de los procesos de recuperación natural y cultural en la Sierra Nevada de Santa Marta. 6 records from Update of the genus Leptochiton (Mollusca: Polyplacophora) in Chilean deep waters: three new reports and description of two new species. 5 records from Neotropical osmylids (Neuroptera, Osmylidae): Three new species of Isostenosmylus Krüger, 1913, new distributional records, redescriptions, checklist and key for the Neotropical species. 525 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 176 records from Jardín Botánico Uniamazonia JBUA. 242 records from Códigos de barras de ADN del marcador COI de aves y tejidos de la colección del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt. 2805 records from Naturalis Biodiversity Center (NL) - Porifera. 213 records from Poliquetos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMUV). 17337 records from UPCB - Herbário do Departamento de Botânica. 429 records from Colección de Referencia de Moluscos del Museo de Ciencias de la Universidad El Bosque. 1369 records from HUCPE - Herbário da Universidade Católica de Pernambuco. 7917 records from Avistajes de espcies de valor especial en áreas protegidas del noreste de Argentina. 16866 records from Gravel Master Thesis / Chubut, Argentina. 1551 records from fundo. 555 records from Collection ornithologique A. Maës. 45 records from Parcela Permanente en el Pantano Martos. 259 records from A taxonomic monograph of the assassin bug genus Zelus Fabricius (Hemiptera: Reduviidae): 71 species based on 10,000 specimens. 2012 records from Caracterización morfométrica del bagre rayado para la cuenca del Magdalena. 3 records from A new species of lizard Placosoma Tschudi, 1847 (Squamata: Gymnophthalmidae) from the relictual forest mountains of the State of Ceará, Brazil. 595 records from Queensland Museum provider for OZCAM. 2 records from ARC-PPRI: Collection of Southern African bees (1800-2007). 3 records from Two new species of South American Glaresidae (Coleoptera: Scarabaeoidea). 50 records from CM Birds Collection. 286 records from Monitoreo biológico en la cuenca Sonso, campaña Agua ARA - RARE - CVC – Asociación Calidris. 6847 records from HURB - Herbário do Recôncavo da Bahia. 1558 records from CUMV Amphibian Collection (Arctos). 9649 records from MBML-Peixes - Coleção de Peixes. 491081 records from Aarhus University Palm Transect Database. 16 records from Myxozoa Collection - Instituto Nacional de Pesquisas da Amazônia. 3 records from A new species of Dohrnemesa from Brazil, with notes on the male of D. carvalhoi and on D. albuquerquei (Hemiptera: Heteroptera: Reduviidae: Emesinae). 35 records from NMSA: Arthropod Collections (1900-2012). 2 records from The land crab Johngarthia planata (Stimpson, 1860) (Crustacea, Brachyura, Gecarcinidae) colonizes human-dominated ecosystems in the continental mainland coast of Mexico. 3220 records from Lund Botanical Museum (LD). 2 records from Specimens of livervort herbarium KPABG. 1 records from Auckland Museum Land Vertebrates Collection. 350089 records from Snow Entomological Museum Collection. 20 records from UWYMV Bird Collection (Arctos). 6677 records from Caracterización de aves asociadas a los cultivos de flores de la Sabana de Bogotá y el Oriente Antioqueño. 91 records from Spider Mites Collection of Jean Gutierrez. 11 records from A new species of inseminating seasonal killifish of the Cynopoecilus melanotaenia complex from southern Brazil (Cyprinodontiformes: Rivulidae). 7553 records from Colección de anfibios y reptiles del Laboratorio de Herpetología de la Universidad del Valle (UV-C). 593 records from Mamíferos voladores laguna El Tinije. 3197 records from Reptile Specimens. 2047 records from HVAT - Herbário do Vale do Taquari. 137 records from Monitoreo biológico en la cuenca Dagua - Subcuenca Bitaco, campaña ARA - RARE - CVC – Asociación Calidris. 3486 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejo de Páramos Frontino-Urrao y Citará. 196342 records from Geographically tagged INSDC sequences. 25 records from Inventario de Murciélagos Buenos Aires, Tauramena, Casanare. 577 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 196 records from Ouellet-Robert entomological collection (QMOR). 162 records from (Appendix B) Total cyst counts, and abundances of Selenopemphix undulata sp. nov. in Pacific Ocean surface samples. 8201 records from Field Museum of Natural History (Botany) Lichen Collection. 1417 records from HCDAL - Herbário Caririense Dárdano de Andrade-Lima. 1 records from On a new species of the rare syllid genus Exogonoides (Annelida, Phyllodocida, Syllidae). 3670 records from TEPB - Herbário Graziela Barroso. 3695 records from Distribution of planktic foraminifera in ODP Site 202-1240 samples. 42 records from (Table 2) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-543. 125 records from Programa para la Conservación Integral de Diez Especies de Plantas Prioritarias del BST. 2 records from Description of two new species and phylogenetic reassessment of Perelleschus O’Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 147 records from The Arthropoda Varia Collection at the Zoologische Staatssammlung München. 3003 records from HTSA - Herbário do Trópico Semiárido. 12267 records from Field Museum of Natural History (Zoology) Fish Collection. 338 records from Fitoplancton de los bloques de exploración de hidrocarburos COL 4 Y 5 del Caribe colombiano. 51 records from USGS PWRC - Native Bee Inventory and Monitoring Lab - World - Bees. 1 records from Description of a new species of Lutosa Walker, 1869 (Orthoptera: Anostostomatidae: Lutosinae) from the Brazilian Atlantic Forest, with biological and behavioral information. 482 records from Arácnidos de Centroamérica. 1 records from The First Parthenogenetic Pleurodont Iguanian: A New All-female Liolaemus (Squamata: Liolaemidae) from Western Argentina. 2352 records from ZUEC-ORT - Coleção de Orthoptera do Museu de Zoologia da UNICAMP. 6 records from Coleção de Entomologia do Museu Nacional / UFRJ. 18430 records from MSB Mammal Collection (Arctos). 20165 records from HVASF - Herbário Vale do São Francisco. 1102 records from Plantas laguna El Tinije. 118 records from MSB Host Collection (Arctos). 243 records from Ghent university - Zoology Museum - Nematod Collection. 12 records from William Nylander lichen collection. 9125 records from Colección de anfibios del Museo de Historia Natural de la Pontificia Universidad Javeriana. 37 records from The fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1651 records from Geographic distribution of dinoflagellate cysts in surface sediments. 105 records from ARC-PPRI: Chalcidoidea Collection (1900-2010). 7 records from A revision of the myrmecophilous genus Smilax Laporte (Coleoptera: Staphylinidae: Staphylininae). 2777 records from HST - Herbário Sérgio Tavares. 11 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1640 records from Coleccion Herpetologica Reptiles LJAMM-CNP. 3782 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en el Complejo de Páramos Perijá. 859 records from LGM, planktic foraminifera (EPILOG version). 4 records from Colección de Herbario. 17 records from Inventarios de Herpetos de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 84 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 19 records from ZUEC-MYX - Coleção de Myxozoa do Museu de Zoologia da UNICAMP. 1474 records from Estudios bióticos: Plantas, anfibios, aves y edafofauna epígea en el complejo de páramo Los Picachos. 2985 records from Colección Entomológica CDMB. 1 records from A new workerless inquiline in the Lower Attini (Hymenoptera: Formicidae), with a discussion of social parasitism in fungus-growing ants.. 60 records from The echinoderm collection (IE) of the Muséum national d'Histoire naturelle (MNHN - Paris). 319 records from R-Tipos - Herbário do Museu Nacional - Tipos. 221 records from Caracterización florística de las ciénagas en Gamarra y Barrancabermeja de 2012. 205 records from The cnidarians collection (IK) of the Muséum national d'Histoire naturelle (MNHN - Paris). 8606 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1060 records from Biodiversidad de grupos funcionales de microorganismos en el Parque Nacional Natural de Los Nevados, Colombia. 51 records from University of Amsterdam (NL) - Páramo Vegetation Research, Bordoncillo - Nariño, Colombia. 7038 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 189 records from Equinodermos de La Guajira Colombiana. 340 records from University of Tennessee at Chattanooga. 1 records from Collections ichtyologiques et herpétologiques (BOUM). 137 records from Catálogo de los equinodermos recientes de México (Fase II). 6 records from NU: KwaZulu-Natal Invasive Alien Species (1821-2011). 1 records from The Fish Database of Taiwan. 203 records from Animal Sound Archive. 6 records from Distribution of two species of Nephropsis Wood-Mason, 1872 (Crustacea, Decapoda, Nephropidae) from northeastern Brazil. 539 records from Crustacea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 507 records from SJRP-Algae - Herbário de algas de São José do Rio Preto. 1 records from Four new species of Chinaia Bruner & Metcalf (Hemiptera: Cicadellidae: Neocoelidiinae) from the Neotropical Region. 569 records from Oregon State Ichthyology Collection. 545 records from Bernice P. Bishop Museum. 20 records from DNSM: Durban Natural Science Museum Insect Collection (1900-2011). 43 records from CUMV Reptile Collection (Arctos). 319 records from Succession of benthic hard-bottom communities abundance at station Errina2012_MDD4. 44805 records from FURB - Herbário Dr. Roberto Miguel Klein. 1668 records from Helechos de la jurisdicción de Corantioquia. 830 records from The birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 387 records from Cowan Tetrapod Collection - Birds. 4080 records from Colección Ictiológica de la Universidad de Antioquia. 1 records from Onychophora Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1089 records from Succession of benthic hard-bottom communities abundance at station Errina2012_IS_solar1. 191 records from Carnet en Ligne. 8787 records from CRI - Herbário Pe. Dr. Raulino Reitz. 90 records from Succession of benthic hard-bottom communities abundance at station Errina2012_IS_solar3. 598 records from HUEG - Herbário da Universidade Estadual de Goiás. 14 records from Sparisoma tuiupiranga, a new species of parrotfish (Perciformes: Labroidei: Scaridae) from Brazil, with comments on the evolution of the genus.. 4 records from Description of a new hygrobatid genus from Chile (Acari, Hydrachnidia: Hygrobatidae). 2 records from World flea collection of Slovenian Museum of Natural History (excluding Slovenia). 13 records from Amphibia collection of the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 27 records from Description of a new species of Characidium Reinhardt, 1867 (Characiformes: Crenuchidae) from the Chapada Diamantina, Bahia, and redescription of Characidium bimaculatum Fowler, 1941. 2 records from ZFMK Sound Archive. 67478 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 239 records from Biodiversidad de los recursos marinos y costeros entre Cartagena y el Golfo de Urabá, Caribe colombiano. 31 records from Actualización de la Colección de Microorganismos de importancia acuática. 171 records from Hormigas de hojarasca asociadas a fragmentos de bosque y cafetales de la zona cafetera de Cundinamarca. 289 records from Odonata del Museo de Entomología de la Universidad del Valle. 61 records from UTEP Vertebrates. 185 records from Succession of benthic hard-bottom communities abundance at station Errina2012_AG. 163 records from Conectividad migratoria de Protonotaria citrea en la costa Caribe de Colombia. 47 records from PACA-Bryophytes - Herbarium Anchieta - Aloysio Sehnem. 6768 records from Composición florística y estructura de dos parcelas permanentes en bosques secos tropicales del municipio de Mendéz, Tolima. 98 records from Condon Fossil Collection. 34 records from Levantamento de Herbáceas da RDS Uatumã. 20336 records from Colección del Herbario PSO de la Universidad de Nariño. 1 records from Phanoceroides Hinton, 1939: description of new species, morphology of larvae, and revised taxonomic position of the genus (Coleoptera: Elmidae) based on molecular evidence. 14520 records from UMMZ Birds Collection. 260 records from CU Invertebrate Paleontology. 107 records from Australian National Insect Collection. 3 records from UFACPZ - Herbário da Universidade Federal do Acre. 7249 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 8979 records from Royal Botanic Garden Edinburgh Herbarium (E). 667 records from Colección de Entomología - Coleoptera. 378 records from Colección de Entomología - Hymenoptera - Aculeata. 6486 records from Hymenoptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 106 records from Michigan State University Herbarium Vascular Plants. 5 records from Colección de Referencia de Reptiles del Museo de Ciencias de la Universidad El Bosque. 3 records from UTEP Mammals (Arctos). 11308 records from ZUEC-PIS - Coleção de Peixes do Museu de Zoologia da UNICAMP. 5263 records from Colección Herpetológica (anfibios) de la Universidad Industrial de Santander. 164 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Arroyo Sauce Grande (Monte Hermoso). 627 records from Botany (UPS). 27 records from (Figure 1) Silicoflagellates at DSDP Hole 69-504. 7 records from The Ando-Patagonian Stigmella magnispinella group (Lepidoptera, Nepticulidae) with description of new species from Ecuador, Peru and Argentina. 6 records from DMNH Birds. 172052 records from Instituto de Ciencias Naturales. 115 records from (Appendix A1) Calcareous nannofossil counts of ODP Site 207-1258. 2 records from MUST, Insecta. 40 records from NRM-Fishes. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 2784 records from CNMT - Herbário Centro Norte Mato Grossense. 46 records from Description of two new species of Avicularia Lamarck 1818 and redescription of Avicularia diversipes (C. L. Koch 1842) (Araneae, Theraphosidae, Aviculariinae) - three possibly threatened Brazilian species. 5 records from Review of Frigitilla Williams in Bartholomay et al., 2015, with description of a new species from Panama (Hymenoptera: Mutillidae). 1 records from DMNS Egg Collection (Arctos). 17 records from Levantamento de Herbáceas do PARNA Jaú. 1685 records from HAS - Herbário Alarich Rudolf Holger Schultz. 344 records from ARC-PPRI: National Collection Of Fungi(1817-2009). 3010 records from Coleópteros de la Colección entomológica del Museo de Historia Natural “Luis Gonzalo Andrade” de la UPTC. 47990 records from Mammalogy Collection - Royal Ontario Museum. 50 records from Fiocruz/CMT - Coleção Micológica de Trichocomaceae. 24 records from Coleção de Ascidiacea do Museu Nacional - UFRJ. 1402 records from Free-living marine Nematodes from Puerto Madryn and Pozo sandy beaches (Chubut, Argentina), 2006.. 61 records from Inventario Murciélagos Finca Naranjito, Aracal, Yopal, Casanare. 3406 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 1132 records from A geographic distribution database of the cassava whitefly complex (Hemiptera, Aleyrodidae) and their associated parasitoids and hyperparasitoids (Hymenoptera). 13 records from Census of Cnidaria (Medusozoa) and Ctenophora from South American marine waters. 15 records from Blattaria Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 2 records from New Genus and species of Heteroxyidae from Brazil (Axinellida: Demospongiae: Porifera), with a revised identification key for the family. 3 records from A new species of Scinax Wagler (Anura: Hylidae) from Paraná, Southern Brazil. 3191 records from Primera caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 3411 records from NMNH Paleobiology Specimen Records. 2398 records from University of Amsterdam (NL) - Páramo vegetation research, Central Andean Cordillera - Colombia. 170192 records from Programa de Observadores a Bordo (POBCh) de la Secretaria de Pesca de la Provincia del Chubut, Argentina . Observer On board Program -Fisheries Secretariat of the Province of Chubut-Argentina (OOBPPCh). 8239 records from MSB Bird Collection (Arctos). 399 records from Macrofauna edáfica de ecosistemas asociados a la cuenca hidrográfica del río Orotoy, Meta. 2 records from Notoraja martinezi sp. nov., a new species of deepwater skate and the first record of the genus Notoraja Ishiyama, 1958 (Rajiformes: Arhynchobatidae) from the eastern Pacific Ocean. 464 records from Bocachico Prochilodus magdalenae (Characiformes: Prochilodontidae) en la cuenca media y baja del río Magdalena. 34374 records from UFPB - Herbário Lauro Pires Xavier - (JPB). 10 records from Laccomimus xikrin sp. nov. and new records of other species of Laccomimus Toledo & Michat, 2015 (Coleoptera: Dytiscidae: Laccophilinae) from Brazil. 42235 records from Insect Occurrence Data from MIZA. 23 records from University of British Columbia Herbarium (UBC) - Fungi Collection. 393 records from FNJV - Fonoteca Neotropical Jacques Vielliard. 44 records from (Table 1) Sulphur chemistry of ODP Site 206-1256 volcanic section. 27 records from Thelyphonida Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 477 records from Coleção de Ictiologia do Museu de Ciências Naturais do Centro Universitário Univates (ZIUMCN-UNIVATES). 398 records from Platynotina (Coleoptera: Tenebrionidae) collections on the World. 12802 records from EAC - Herbário Prisco Bezerra. 1 records from The Neotropical annual killifish genus Pterolebias Garman (Teleostei: Cyprinodontiformes: Rivulidae): phylogenetic relationships, descriptive morphology, and taxonomic revision.. 9 records from Fourteen new species of Heterospilus Haliday (Hymenoptera, Braconidae: Doryctinae) from Brazil. 6 records from Descriptions, transference and new records of Lamiinae from Central and South America (Coleoptera, Cerambycidae). 33 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 11 records from Amphibians and Reptiles collection at the Natural History Museum of Denmark (SNM). 13208 records from Coleção Ictiológica (MNRJ), Museu Nacional (MN), Universidade Federal do Rio de Janeiro(UFRJ). 22 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 6296 records from Colección de peces y macroinvertebrados del Museo de Historia Natural de la Pontificia Universidad Javeriana. 395 records from (Appendix C) Total cyst counts, and abundances of Selenopemphix undulata sp. nov. in ODP Site 202-1233. 45890 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 8071 records from Colección de anfibios - Museo de Herpetología de la Universidad de Antioquia. 692 records from Colección de peces marinos del mar argentino y aguas adyacentes del INIDEP. 6373 records from Herbario de la Universidad Industrial de Santander. 749 records from Colección de Entomología - Heteroptera. 3669 records from R - Herbário do Museu Nacional. 51063 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 5608 records from Herpetology Collection - Royal Ontario Museum. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 17388 records from CAS Herpetology (HERP). 14 records from A new species of the freshwater fish genus Astyanax (Ostariophysi: Characidae) from the rio Iguacu basin, southeastern Brazil.. 433 records from Caracterización de las coberturas vegetales en el gradiente altitudinal Páramo-Bosque en los complejos de Páramo de Guerrero y Altiplano Cundi-boyacense. 3056 records from MBML-Repteis - Coleção de Répteis. 3165 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Santuario de Flora y Fauna Los Colorados. 945 records from Inventario de Aves Mámbita. 8306 records from HUESB - Herbário da Universidade Estadual do Sudoeste da Bahia. 26080 records from Ictiologia Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 266 records from Registros de flora de las caracterizaciones rápidas de coberturas en los municipios de Beltrán y Guataquí, Cundinamarca. 3 records from Entomological specimens of Museum fuer Naturkunde und Vorgeschichte Dessau. 10 records from Vascular plant herbarium, Tromsø Museum. 6818 records from Colección de artrópodos del PNN Gorgona - Museo de Entomología de la Universidad del Valle (MUSENUV). 17129 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 4 records from Neotropical spittlebugs related to Neaenini (Hemiptera, Cercopidae) and the origins of subfamily Cercopinae. 56 records from Arachnida e Myriapoda Museu Nacional (MNRJ ARAC). 9 records from Rivulus uakti sp. n. and R. amanapira sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): two new species from the upper Rio Negro, Brazilian Amazon.. 6466 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 511 records from Arachnida of Costa Rica (INBio). 31144 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 2 records from Two new species of Baeus (Hymenoptera: Scelionidae) from southeastern Brazil parasitoids of Anelosimus (Araneae: Theridiidae).. 2 records from Revisionary studies on the attine ant genus Trachymyrmex Forel. Part 3: The Jamaicensis group (Hymenoptera: Formicidae).. 84 records from Vascular plant herbarium, NTNU University Museum. 1738 records from (Table 2) Relative abundance of planktonic foraminifera species in Pliocene - Early Quaternary sediments from ODP Hole 111-677A. 5314 records from Dados da ocorrência de plantas lenhosas em um gradiente de perturbação/precipitação em área de Caatinga, Parque Nacional do Catimbau, Buíque, PE, Brasil. 447 records from Orthoptera del Museo de Entomología de la Universidad del Valle. 4836 records from Colección de Reptiles - Museo de Herpetología de la Universidad de Antioquia. 6686 records from Observaciones de Especies Silvestres (by Charif Tala). 347643 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 10 records from Culture Collection of Microalgae and Zygnematophyceae Collection Hamburg (MZCH-SVCK). 171 records from Hymenoptera. 14 records from Description of a new species of Euptychia Hübner, 1818 (Lepidoptera: Nymphalidae: Satyrinae) from the western Andes. 778 records from Colección de Entomología - Hymenoptera - Parasitica. 12810 records from AUM Fish Collection. 6116 records from Global compendium of Aedes aegypti occurrence. 1 records from Código de barras genético de cinco grupos críticos de la flora de México. 1 records from Worldwide revision of the genus Fraseroscyphus Boero and Bouillon, 1993 (Cnidaria: Hydrozoa): an integrative approach to establish new generic diagnoses. 9589 records from (Appendix) Distribution of planktonic foraminifers at DSDP Hole 72-516F, Coniacian-Santonian to upper Maestrichtian. 7443 records from Free-living marine Nematodes from San Antonio bay (Río Negro, Argentine) 2009.. 1 records from Las monocotiledóneas mexicanas, una sinopsis florística. Parte II. 6148 records from Natural History Museum Rotterdam (NL) - Insecta collection. 58 records from NCSM Herpetology Collection. 12 records from Proposal of Kupiuka and Plesiopiuka, two new genera of jumping spiders from Brazil (Araneae: Salticidae: Heliophaninae). 510 records from USGS Nonindigenous Aquatic Species database. 214 records from Wilson Botanical Garden - Las Cruces Biological Station. 3010 records from SLUI - Herbário Rosa Mochel. 1076 records from Escarabajos coprófagos (Scarabaeidae: Scarabaeinae) del eje cafetero Colombiano. 5 records from Deep-sea (> 1000 m) Goniasteridae (Valvatida; Asteroidea) from the North Pacific, including an overview of Sibogaster, Bathyceramaster n. gen. and three new species. 84 records from NCSM Invertebrates Collection. 91433 records from UB - Herbário da Universidade de Brasília. 3 records from Tropidomyrmex elianae, a new myrmicine ant genus and species from Brazil, tentatively assigned to Solenopsidini (Hymenoptera, Formicidae).. 47 records from Actualización de la Colección de Collembola de México y ácaros edáficos. Catálogo de oribátidos de México. 15 records from Two new emerald geometrid species of Telotheta Warren from Ecuador and Bolivia (Lepidoptera: Geometridae, Geometrinae, Lophochoristini). 32 records from The Hemiptera collection (EH) of the Muséum national d'Histoire naturelle (MNHN - Paris). 6 records from Green Plant Herbarium (TRT). 185 records from Naturalis Biodiversity Center (NL) - Mollusca. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 1 records from Conservación de la población de Loro Orejiamarillo (Ognorhynchus icterotis) en el piedemonte llanero, departamento del Meta. 708 records from Occurrences des observations de la campagne REMMOA Guyane (2008). 17 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña diciembre 2010. 930 records from ZUEC-ARA - Coleção de Aracnideos do Museu de Zoologia da UNICAMP. 27 records from Análisis ecológico de la mastofauna en la parte alta del Rio Güangui. 4711 records from The crustaceans collection (IU) of the Muséum national d'Histoire naturelle (MNHN - Paris). 7847 records from PEUFR - Herbário Professor Vasconcelos Sobrinho. 3 records from New species of Graphocaecilius Enderlein (Psocodea: ‘ Psocoptera’: Lachesillidae) from Colombia. 4924 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2007. 23 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña noviembre 2006. 10 records from Systematics of the family Ariidae (Ostariophysi, Siluriformes), with a redefinition of the genera.. 1664 records from ZUEC-AVE - Coleção de Aves do Museu de Zoologia da UNICAMP. 177 records from (Appendix) Ostracodes at DSDP Leg 72 Holes. 1083 records from Diversidad de Mariposas en la Reserva Natural El Romeral. 2 records from Two new genera and five new species of Tullbergiidae (Collembola) from the southern Appalachian Mountains of North America, with redescription of Tullbergia clavata Mills. 89 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B. 50600 records from KUBI Herpetology Collection. 2992 records from Australian Museum provider for OZCAM. 2965 records from Herbarium - Las Cruces Biological Station. 5 records from ZUEC-API - Coleção de Apicomplexa do Museu de Zoologia da UNICAMP. 1995 records from Monitoreo y morfometría de la avifauna de la Universidad del Valle 2011-2012. 266 records from Speothos Venaticus por Guillermo Gil. 913 records from Colección de Entomología - Orthoptera. 177494 records from Segundo censo de plantas leñosas de una Parcela Permanente de 25 hectáreas, ubicada en la Reserva Natural La Planada (Nariño, Colombia). 274 records from Detection histories for eight species of Amazona parrots in Venezuela during the NeoMaps bird surveys in 2010. 12040 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 1453 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales de afloramiento rocoso del Parque Nacional Natural El Tuparro. 76 records from Colección de Referencia de Cnidarios del Museo de Ciencias de la Universidad El Bosque. 15 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 4558 records from Herbario virtual bosques secos de Colombia - sección herbario FMB (IAvH). 3828 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 550 records from Colección de Referencia de Macroinvertebrados Bentónicos del Museo de Ciencias de la Universidad El Bosque. 4469 records from Registros de hongos en áreas protegidas de la Argentina. 167 records from Allan Herbarium (CHR). 8373 records from IRAI - Herbário do Parque da Ciência Newton Freire Maia. 1677 records from NOAA Deep Sea Corals Research and Technology Program. 2 records from Technomyrmex (Formicidae: Dolichoderinae) in the New World: synopsis and description of a new species.. 5 records from Cowan Tetrapod Collection - Herpetology. 16321 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Mammalogy National Collection (MACNMa).. 4 records from Cliona acephala (Porifera: Demospongiae: Clionaida), a new encrusting excavating reef sponge from the Colombian Caribbean belonging to the Cliona viridis species complex. 882 records from Entomology at ZMUC, Natural History Musem of Denmark. 3 records from Palaeobiology - Vertebrate Fossils Collection - Mammalia - Royal Ontario Museum. 534 records from SORO - Herbário do Centro de Ciências e Tecnologias para a Sustentabilidade. 339 records from Fiocruz/CLIOC - Coleção de Leishmania. 1700 records from HPL - Herbário do Jardim Botânico Plantarum. 4 records from BoBO - Botanic Garden and Botanical Museum Berlin-Dahlem Observations. 31488 records from Neptune Deep-Sea Microfossil Occurrence Database. 19 records from A review of the genus Scaponopselaphus Scheerpeltz (Insecta: Coleoptera: Staphylinidae). 6954 records from VERTEBRADOS DE VALOR ESPECIAL EN ÁREAS PROTEGIDAS DE LA ARGENTINA. 3 records from Trichomycterus santanderensis: A new species of troglomorphic catfish (Siluriformes, Trichomycteridae) from Colombia.. 6859 records from Hormigas del Museo de Entomología de la Universidad del Valle. 538 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 1245 records from Registros Primates Neotropicales Convocatoria APC. 2 records from A review of the genus Garra Hamilton 1822 of Bhutan, including the descriptions of two new species and three additional records (Cypriniformes: Cyprinidae). 1 records from Studies of Peruvian Ptiliidae (Coleoptera) 5: Chaska nawi, a new genus and species of Acrotrichinae, Acrotrichini. 1 records from Two new troglobiotic palpigrades (Palpigradi: Eukoeneniidae) from Brazil. 54578 records from CEN - Herbário da Embrapa Recursos Genéticos e Biotecnologia. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 10258 records from MVZ Bird Collection (Arctos). 84 records from Orchid Herbarium Collection. 204 records from Vascular Plant Herbarium, Oslo (O). 20 records from Colección de Referencia de Anfibios del Museo de Ciencias de la Universidad El Bosque. 4 records from (Table 2) Benthic isopod species of the Ross Sea, their bathymetry and distribution in the Southern Ocean. 119219 records from Occurrences in SinBIOTA. 32 records from Succession of benthic hard-bottom communities abundance at station Errina2012_CS. 17 records from Coleção de Brachiopoda do Museu Nacional - UFRJ. 24 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 4494 records from University of Amsterdam (NL) - Páramo Vegetation Research, Sumapaz-Bocagrande-Chisaca paramo complex, Colombia. 216 records from Monitoreo biológico en la cuenca Dagua - Subcuenca La Guinea ARA - RARE - CVC – Asociación Calidris. 1050 records from ZUEC-COL - Coleção de Coleoptera do Museu de Zoologia da UNICAMP. 7515 records from KUBI Ornithology Collection. 1108 records from Anymals+plants - Citizen Science Data. 1034 records from (Table 3) Distribution of Campanian-Maestrichtian calcareous foraminifers in DSDP Hole 78-543A. 1620 records from Herbario virtual bosques secos de Colombia - Sección herbario TULV (INCIVA). 2 records from First record of Viannaiidae (Nematoda: Trichostrongylina) in fossorial rodents (Ctenomys spp.) from Central Argentina, with description of a new genus and species. 1061 records from Colección Ornitológica Universidad de Nariño. 2 records from Systematic studies of the genus Aegialomys Weksler, Percequillo and Voss, 2006 (Rodentia: Cricetidae: Sigmodontinae): Annotated catalogue of the types of the species-group taxa. 1 records from The Shiny Cowbird, Molothrus bonariensis (Gmelin, 1789) (Aves: Icteridae), at 2,800 m asl in Quito, Ecuador. 220 records from Coleção de Bryozoa do Museu Nacional - UFRJ. 2388 records from Lichen herbarium, Tromsø Museum. 1 records from Herbario de Briófitos de la Universidad de Salamanca: SALA-Bryo. 138 records from E. C. Smith Herbarium (ACAD). 24 records from Two new species of Caenis Stephens, 1835 (Ephemeroptera: Caenidae) from South America. 66 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en el Parque Provincial Salto Encantado (Guller et al.a, marzo 1997). 637 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales de Bahía Málaga, municipio de Buenaventura, Valle del Cauca. 9 records from UAIC Ichthyological Collection. 348 records from Colección de referencia del Herbario CUVC de la Universidad del Valle. 1 records from LEXEY RESHCHIKOV & ILARI EERIKKI SÄÄKSJÄRVI (2015) Seven new species of the genus Physotarsus Townes 1966 (Hymenoptera, Ichneumonidae) from South America. Zootaxa, 3972 (1): 026 - 042.. 238 records from Colección de referencia de otolitos, Instituto de Ciencias del Mar-CSIC. 2 records from The Genus Criodion (Audinet-Serville, 1833) (Coleoptera, Cerambycidae): First Record for Panama. 5 records from Taxonomic review of the species of Helina R. - D. (Diptera: Muscidae) from Andean-Patagonian forests. 22 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 2 records from Two new, brachypterous Limnellia species from the Venezuelan Andes (Diptera: Ephydridae). 11 records from A new species of Jupiaba Zanata, 1997 (Ostariophysi, Characiformes, Characidae) from the rio Tocantins drainage, Brazil.. 19345 records from Fungi of Costa Rica (INBio). 1 records from New species of Zenoria Mulsant (Coleoptera: Coccinellidae) from Brazil and Peru. 8 records from Diaphoromyrma, a new myrmicine ant genus (Hymenoptera: Formicidae) from North Eastern Brazil. 89 records from NCSM Mammals Collection. 4 records from Wrapped in flames: Corydoras hephaestus, a new remarkably colored species from the Rio Madeira basin (Teleostei: Callichthyidae). 83 records from New distributional data on aquatic and semiaquatic bugs (Hemiptera: Heteroptera: Gerromorpha & Nepomorpha) from South America. 1665 records from Colección Ictiológica de la Universidad Industrial de Santander. 3037 records from HDJF - Herbário Dendrológico Jeanine Felfili. 2651 records from Caracterización de la vegetación en los sectores de Aipe (Huila), Yaví (Tolima) y Dagua (Valle del Cauca), como insumo para la identificación de oportunidades de conservación y la recuperación de servicios ecosistémicos del bosque seco. 152 records from Investigación y manejo para la conservación de tortugas amenazadas de los humedales llaneros. 10 records from Succession of benthic hard-bottom communities abundance at Liliguapi in 2010. 420 records from Monitoreo biológico en la cuenca La Paila, campaña ARA - RARE - CVC – Asociación Calidris. 28056 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 2 records from Hemiptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 942 records from Herbario HUAZ Enrique Forero. 337 records from Caracterización de coberturas vegetales en el páramo de Santurbán. 19454 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 1 records from UAM Insect Observations (Arctos). 28118 records from UF FLMNH Ichthyology. 25 records from Auckland Museum Marine Collection. 9832 records from Escarabajos coprófagos (Coleoptera: Scarabaeidae: Scarabaeinae) de bosques secos Colombianos de la Colección Entomológica del Instituto Alexander von Humboldt. 1 records from The Pisces Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. 33458 records from BHCB-SL - Herbário UFMG - Samambaias e Licófitas. 45 records from New Zealand Fungal and Plant Disease Collection (PDD). 3 records from A new species of Pachyurus Agassiz 1831 (Teleostei: Perciformes: Sciaenidae) from the Río Napo basin, Eastern Ecuador.. 10 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Paleopalynology National Collection (BAPal).. 3 records from The ant genus Linepithema (Formicidae: Dolichoderinae) in Colombia. 81 records from Aves del Santuario de Fauna y Flora Malpelo entre 2006 y 2013. 17 records from Thirteen new records of ferns from Brazil. 458 records from EAN - Herbário Jaime Coelho de Moraes. 376 records from Levantamento do estrato arbustivo da vegetação de campina do RDS Uatumã. 26 records from Colección de Referencia de Mamíferos del Museo de Ciencias de la Universidad El Bosque. 21 records from Revision of the myrmicine ants of the Adelomyrmex genus-group (Hymenoptera: Formicidae).. 9 records from Sponge epizoism in the Caribbean and the discovery of new Plakortis and Haliclona species, and polymorphism of Xestospongia deweerdtae (Porifera). 2 records from The uncommon Neotropical genus Pazius Navás, 1913 (Mecoptera: Bittacidae): a comprehensive synthesis, with description of a new Brazilian species. 2 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 436 records from The Coleoptera collection (EC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 43 records from Inventarios de Murciélagos de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 4007 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2006. 195 records from ZUEC-APL - Coleção de Aplacophora do Museu de Zoologia da UNICAMP. 6927 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 3362 records from Marine Invertebrate from Argentina, Uruguay and Chile. 270 records from Monitoreo biológico en la cuenca RUT, campaña ARA - RARE - CVC – Asociación Calidris. 17156 records from Cicadelidos (Hemiptera: Cicadellidae) de Colección Entomológica del Instituto Alexander von Humboldt. 16 records from Inventario de Murciélagos Floreña I, Yopal, Casanare. 968 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 1076 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Tuluá, Valle del Cauca. 165 records from Diversidad florística y estado de conservación en dos ventanas de paisaje de la UPR Tunjuelo priorizadas: Usme y Ciudad Bolivar, Bogotá. 6 records from Diptera. 6423 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 4 records from A new species of Microglanis Eigenmann, 1912 (Siluriformes, Pseudopimelodidae) from rio São Francisco basin, Brazil.. 643 records from Invertebrates (Type Specimens) of the Swedish Museum of Natural History. 26554 records from SP-Bryophyta - Maria Eneyda P. Kauffman Fidalgo. 1 records from UWYMV Mammal Collection (Arctos). 338 records from Fundación Miguel Lillo - Colección Criptogámica. 1 records from MVZ Herp Observations (Arctos). 1015 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Macuira. 2363 records from Avifauna en un área perturbada del bosque andino en el Parque Nacional Natural Farallones de Cali, corregimiento de Pance, Valle del Cauca (Colombia). 22 records from Páramo de Belmira as an important centre of endemism in the northern Colombian Andes: new evidence from Pronophilina butterflies (Lepidoptera: Nymphalidae, Satyrinae, Satyrini). 3623 records from SysTax - Herbaria. 14024 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 6081 records from Censos de aves del parque nacional Laguna Blanca. 78838 records from Geneva Herbarium – General Collection (G). 12 records from First description of the male of the spider Tibellus paraguensis Simon, 1897 (Araneae: Philodromidae), with new distribution records. 6222 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 19 records from Colección de Referencia de Poríferos del Museo de Ciencias de la Universidad El Bosque. 314 records from University of Amsterdam (NL) - Páramo Vegetation Research, Paramo "El Almorzadero", Colombia. 207014 records from Instituto de Botánica Darwinion. 17 records from New distribution records of the savanna specialist fungus-farming ant Cyatta Sosa-Calvo et al. (Hymenoptera: Formicidae: Myrmicinae). 941 records from Opiliones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 909 records from JOIw - Xiloteca Joinvillea. 7892 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 2791 records from SJRP - Herbário de São José do Rio Preto. 3 records from A synopsis of the subgenus Centris (Hemisiella) Moure, 1945 (Hymenoptera: Apidae: Centridini) in Colombia, with description of a new species. 4837 records from Free-living marine Nematodes from San Antonio and Cormoranes sandy beaches (Rio Negro, Argentina), 2006.. 3 records from MVZ Mammal Observations (Arctos). 5 records from New records of two endemic troglobitic and threatened arachnids (Amblypygi and Opiliones) from limestone caves of Minas Gerais state, southeast Brazil. 400 records from Herbario Virtual Bosques Secos de Colombia - Sección Herbario Universidad de Córdoba (HUC). 1 records from AMNH Invertebrate Paleontology Collection. 5046 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 3019 records from UFMT - Herbário UFMT. 9064 records from CAS Botany (BOT). 286 records from CUMV Bird Collection (Arctos). 878 records from Angelo State Natural History Collections (ASNHC) - Mammalogy Collection. 118 records from Amblypygi Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 3 records from Latheticomyia Wheeler (Diptera: Pseudopomyzidae) from Peru: new species, description of the male of L. longiterebra Hennig and a key to species. 16152 records from CPAP - Herbário CPAP. 84 records from ZUEC-HOL - Coleção de Holothuroidea do Museu de Zoologia da UNICAMP. 183 records from South Australian Museum Australia provider for OZCAM. 120 records from Computarización de la base de datos del Banco Nacional de Germoplasma Vegetal - Fase 2. 15 records from Inventario de Herpetología Buenos Aires, Tauramena, Casanare. 346 records from International Fossil Shell Museum (NL) - Mollusca Collection. 408 records from Censo del Zarapito Trinador (Numenius phaeopus) y Otras Aves Acuáticas en el Parque Nacional Natural Sanquianga. 10 records from New species of Dichogaster Beddard, 1888 (Clitellata: Benhamiidae) with additional records of earthworms from Guadeloupe (French West Indies). 182 records from Lichen herbarium, UiB. 2403 records from ZUEC-CLB - Coleção de Collembola do Museu de Zoologia da UNICAMP. 504 records from Dieta y preferencias alimenticias de poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en Paz de Ariporo, Casanare. 1866 records from Acari Collection - Instituto Nacional de Pesquisas da Amazônia. 325 records from Colección de Entomología - Coleoptera - Chrysomeloidea. 496 records from Macroinvertebrate abundance in montane tropical streams of varying land-use, Ecuador. 49 records from ISU Birds. 11729 records from HEPH - Herbário Ezechias Paulo Heringer. 1 records from Solifugae Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 3 records from Description of a new species of Namalycastis (Annelida: Nereididae: Namanereidinae) from the Brazilian coast with a phylogeny of the genus. 2954 records from Establecimiento de línea base para el monitoreo de especies de plantas de interés para la conservación. 3678 records from BHZB - Herbário do Jardim Botânico da Fundação Zoo-Botânica de Belo Horizonte. 1186 records from Inventarios de Fauna y Flora en Relictos de Bosque en el Enclave Seco del Río Amaime, Valle del Cauca. 10863 records from MOSS - Herbário Dárdano de Andrade Lima. 7035 records from HRCB - Herbário Rioclarense. 16 records from Inventarios de Aves de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 408 records from SJRP-Pteridophyta - Herbário de Pteridophyta de São José do Rio Preto. 5039 records from PACA-AGP - Herbarium Anchieta. 1181 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 7 records from Hydrolagus matallanasi sp. nov. (Holocephali, Chimaeridae) a new species of rabbitfish from southern Brazil.. 1 records from Checklist of the earthworms (Oligochaeta) of Kerala, a constituent of Western Ghats biodiversity hotspot, India. 17612 records from SP-Fungi - Maria Eneyda Pacheco Kauffmann Fidalgo. 8044 records from UESC - Herbário Universidade Estadual de Santa Cruz. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences